Ultrastructural characterization of the egg chorion and reproductive anatomy of potato tuber moth, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) - Pranita Roy; Suresh R. Jambagi; K. Logeswaran; Doddachowdappa Sagar; M. Mohan; G. Mahendiran; D. Nandhini (Tissue and Cell, 2027)

EBV-informed multi-omics target prioritization and structure-based drug repurposing reveal potential therapeutic strategies for multiple sclerosis - Nevil M. Lal; Harshit Sajal; Aswin Mohan; Asna R.; Fadiya Fathima; Rajesh Raju; Anuroopa G. Nadh (Functional & Integrative Genomics, 2026)

MicroRNAs in dilated cardiomyopathy: from biomarkers to therapeutic targets - Abisha Vince Jeo V S; P. S. Sneha Sandra; Mahesh Mundalil Vasu; Jeemon Panniyammakal; Sanjay Ganapathi; Madhusoodanan Urulangodi; Neethu Mohan; P. R. Anil Kumar; Srikant Ambatipudi; Jyothi Vijay; Sivadasanpillai Harikrishnan (Molecular Biology Reports, 2026)

An explainable deep learning-integrated decision support system for field diagnosis and management of botrytis grey mold in castor - G. Jadesha; Yamanura Madival; R. Mohan Kumar; Anurag Dhole; H.C. Lohithaswa; Mallana Gowda Mallikarjuna; K.B. Palanna; D. Deepak (Computers and Electronics in Agriculture, 2026)

Rice immunity against Asian rice gall midge: from resistance genes to precision breeding - G. Rakesh; B. Vidhyadhar; Y. Chandra Mohan; Yadla Hari; R. Shravan Kumar; P. Gonya Naik; B. Manju Bhargavi; G. Anil kumar; M. Saicharan; Ramya Rathod (Cereal Research Communications, 2026)

Normalization of candidate reference genes for precise qRT-PCR quantification in Maruca vitrata F. (Lepidoptera: Crambidae) under multiple biotic and abiotic stress regimes - C. R. Chandana; Sushila Nadagouda; Muthugounder Mohan; A. Sunny Rao; Basavaraj S. Kalmath; Shivaleela Gouda; Jayaprakash M. Nidagundi; Saroja Narsinga Rao (International Journal of Tropical Insect Science, 2026)

Improving sustainable water usage in extensive shrimp aquaculture in Bangladesh - Kelly Thornber; Mohammad Mahfujul Haque; Muhammad Abdur Rouf; Tamanna Fardoshi; Neaz A. Hasan; Md Rony Golder; Abul Bashar; Partho Pratim Debnath; Muhammad Meezanur Rahman; David Kawahigashi; Vishnumurthy Mohan Chadag; Charles R. Tyler (Aquaculture, 2026)

Mimosa pudica Linn. - An important medicinal plant: Pharmacognostic evaluation, bioactive compound isolation, structural elucidation, and in silico analysis - Kousik Ghosh; Karthick Gopal; Lakshmanan Narayanan; Vamsee Krishna K․; Akansha Pandey; Aswathi Mohan P․; Siva Surya; Suseem S R; S. Chitra; Preeti Sharma; Ajay Kumar Meena (Next Research, 2026)

Spatiotemporal trajectories of built-environment using centroid shift model: a directional understanding of urban evolution - Ashritha Keerthikumar; Gopal R. Patil; Krishna Mohan Buddhiraju (Applied Geomatics, 2026)

Biocontrol potential of Trichoderma and Bacillus strains against Macrophomina phaseolina causing dry root rot in groundnut - Prince Jayasimha Pamala; R. Sarada Jayalakshmi; K. Vemana; G. Mohan Naidu; Rajeev K. Varshney; Hari Kishan Sudini (Journal of Plant Pathology, 2026)

Molecular and functional analysis of RNAi machinery genes in a neuropteran insect predator, Chrysoperla zastrowi sillemi - V. S. Chinnu; M. Mohan; R. Manjunatha; P. J. Aneesha; Suresh R. Jambagi (BioControl, 2026)

Linking environmental DNA and acoustic telemetry to monitor Striped Bass (Morone saxatilis) in an estuarine ecosystem - Kade O. Tyrrell; Emily R. Lancaster; Benjamin P. Gowell; Josephine M. Pikowski; Charles E. Tilburg; John A. Mohan; Markus Frederich (Marine Environmental Research, 2026)

Direct reduction of low-grade taconite ore by atmospheric-pressure, microwave-powered hydrogen plasma - Vivek Pachchigar; Prashant Kumar Barnwal; Tanishka Kucheria; Daniel S. Ellis; Ivan Shchelkanov; Robert Stubbers; Brett Spigarelli; Brian Jurczyk; Jessica A. Krogstad; R. Mohan Sankaran (Minerals Engineering, 2026)

Integrated enzyme-assisted hot water biorefinery for enhanced recovery of bioactive compounds from brown seaweeds - C. S. Tejpal; S. M. Vijayakumar; K. M. Pradeep; Rahman K. Habbeb; T. G. Sumithra; C. O. Mohan; T. K. Anupama; R. Anandan (Journal of Applied Phycology, 2026)

Redefining coastal and marine boundaries through a 50-NM functional threshold for integrated ocean governance - P. Ragavan; R. Ramesh; Sundeep; K. Kathiresan; P. M. Mohan (Hydrobiologia, 2026)

Isotopic signatures of Heliconoides inflatus and Globigerinoides ruber for tracing calcification depth and upper ocean conditions in the Bay of Bengal and Andaman Sea - E. Sreevidya; A.V. Sijinkumar; L. Reuning; G. Xydis; N.N.S. Vishnu; N. Andersen; B. Nagender Nath; R. Mohan; N. Keul (Marine Micropaleontology, 2026)

Genomic analysis identifies unreported adaptive mutations in monkeypox virus immune evasion genes - Ann Steffi Sharon John; Mirudhula Kamakshi Mohan Ramaswamy; Harihar Balasubramanian; Karthick Selvaraj; Thenmozhi Marudhadurai; M. R. Asraf Sithikka; Gayathri Elangovan; Manojkumar Kumaran; Suvaiyarasan Suvaithenamudhan; Konda Mani Saravanan (Virus Genes, 2026)

Neem extract-mediated green reduction of Ag, Cu, and Fe onto g-C3N4 photocatalysts for LED-light-driven multipollutant degradation and H2 generation - R. Vijayarangan; Anupamaraj Kizhakke Purayil; Sakar Mohan; R. Ilangovan (Journal of Water Process Engineering, 2026)

Application of time-domain electromagnetic data in 3D mapping of buried paleochannels hosting sandstone type uranium mineralization in Satpura Gonwana basin, India - M. Sridhar; A.K. Maurya; Amaresh Kumar; Rakesh Mohan; Srinjoy Mukharjee; S.K. Dash; R. Mamallan (Journal of Applied Geophysics, 2026)

Sustainable practices to combat water crises: Assessing impacts of direct recycled water versus indirectly recharged groundwater on agroecosystem health - Kavita Verma; Manjari Manisha; Shwetha J; Ramesh N; Rohan HS; Mohan Kumar MS; Chanakya HN; Parama V. R. R; Sarala Kumari J; Lakshminarayana Rao (Groundwater for Sustainable Development, 2026)

Metformin for knee osteoarthritis in overweight and obese adults: a systematic review and meta-analysis of efficacy, safety, and disease-modifying anti-inflammatory potential - Santenna Chenchula; Krishna Chaitanya Amerneni; R. Padmavathi; K. Anitha; Mohan Krishna Ghanta; Shriraam Karunakaran; Shubham Atal; Sunil Kumar; Pavani Saggurthi; Shoibam Jenifa; K. Mythili Bai; Madhavrao Chavan; et al. (Inflammopharmacology, 2026)

Derivation of seawater quality criteria for copper, cadmium, zinc, and mercury for the coastal and coral reef ecosystems of Gulf of Mannar, India - C M Ramakritinan; M Anand; L Palanikumar; Manoj Singh; S Manikandan; G Jayanthi; A K Kumaraguru; D Mohan; T Balasubramanian; B R Subramanian (Journal of Earth System Science, 2026)

Dual‐Channel Temporal Graph Attention Network for Forecasting Sodium Hazard in Irrigation Water Systems - A. M. Arun Mohan; B. Senthilnayaki; K. R. Mohan Raj; Verma (Irrigation and Drainage, 2026)
Groundwater quality for irrigation is increasingly threatened by overextraction, salinization and agricultural intensification, yet existing sodium hazard prediction methods often fail to capture complex temporal and relational dynamics. This study proposes a Dual‐Channel Temporal Graph Attention Network (DC‐TGAN), integrated with advanced preprocessing and hybrid feature selection, to enhance the prediction of farming water quality characteristics—Kelly's ratio (KR), residual sodium carbonate (RSC), sodium adsorption ratio (SAR), and %sodium (%Na)—in Southern Rajasthan, India's Pratapgarh district. The approach's originality is found in its ability to simultaneously model multivariate spatiotemporal dependencies and optimize convergence through Quokka Swarm Optimization. The model was found to best predict groundwater when using 10 years (2010–2020) of groundwater data, with correlation coefficients ( R 2 ) near to 1.0 and testing RMSE of 0.04 in KR and 0.16 in SAR. On the whole, the DC‐TGAN was superior to the models of random forest, ANN, LSTM and WDO‐ANN with an accuracy of 99.8%, F1‐score of 99.7%, and the T of 0.02 s. These findings indicate that the model can be viewed as a powerful and scalable instrument of timely identifying sodium hazards to contribute to sustainable groundwater management and irrigation planning in semiarid areas.

Experimental investigation on nano-modified metakaolin based quaternary blended concrete for sustainable urban flood management - Kotteeswaran Santhanam; J. UshaKranti; Ayinala Naga Sai; A. Mohan; R. Abirami (Innovative Infrastructure Solutions, 2026)

Whole Mitochondrial Genome Analysis Highlights India’s Role in Pig Domestication and Maternal Lineage Diversification - Sonika Ahlawat; Upasna Sharma; Karan Veer Singh; Reena Arora; Rekha Sharma; Ajay Singh; N. H. Mohan; Santanu Banik; Raja KN; R. T. Venkatachalapathy (Biochemical Genetics, 2026)

Initial results of the novel acoustic-based apparatus to measure cumulative rainfall and its intensity - Shijo Zacharia; K S Hosalikar; Mrutyunjay Mohapatra; Manish R Ranalkar; Anjith Anjan; U K Shende; K N Mohan (Journal of Earth System Science, 2026)

Carbon sequestration potential of Himalayan Cypress stands of Kumaun Central Himalaya, India - Disha Upreti; Lalit Mohan Tewari; Ashish Tewari; Naveen Chandra Pandey; R. K. Chaturvedi (Tropical Ecology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Multi-paleoclimatic proxies implicate climate shift from arid-to-humid in the Northeastern Arabian Sea teleconnected to ENSO events - Sruthy Rose Baby; Mohan Kuppusamy; Busnur R Manjunatha; Jithin Jose; Pankaj Kumar; Saravanan Kothandaraman; Ravi Mishra (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

High levels of Bt cry toxin resistant allele frequency in South Indian populations of cotton pink bollworm, Pectinophora gossypiella Saunders (Gelechiidae: Lepidoptera) - Suresh R. Jambagi; M. Mohan; T. Venkatesan; K. Muralimohan; D.N. Kambrekar; C.P. Mallapur; Neenu Augustine (Journal of Invertebrate Pathology, 2026)

Isolation and whole-genome characterization of multidrug-resistant Acinetobacter baumannii from Indian retail meat: unveiling high-risk clones and zoonotic transmission threats via comparative genomics - Vanishree B.; Wilfred Ruban Savariraj; Mohan H. V.; Jaganatha Rao; Porteen Kannan; Anbazhagan Subbaiyan; Sureshkannan S.; Nidhi Sudhakaran P.; Nithya Quintoil M.; Sivachandiran R.; Sivaraman Gopalan Krishnan; Raghavendra G. Amachawadi (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Urdamycin V from Streptomyces sp induces p53 independent apoptosis in cervical cancer cells inconsiderate of HPV status and inhibited growth of gram-positive human pathogens - Vipin Mohan Dan; Rahul Sanawar; Gama M. G. Mohan; Soniya P. Cheriyan; Thankayyan R. Santhosh Kumar (Natural Product Research, 2025)

Genome editing of detoxification gene repertoires in insects using clustered regularly interspaced short palindromic repeats (CRISPR): A systematic review and meta-analysis - Vinithashri Gautam; Suresh R. Jambagi; Mohan Muthugounder (Pesticide Biochemistry and Physiology, 2025)

Dynamics of Total organic carbon: Partitioning, distribution and controlling processes in the Indian sector of the Southern Ocean during austral summer - Melena A. Soares; V. Venkataramana; R.K. Mishra; P. Sabu; R.K. Naik; Manish Tiwari; N. Anilkumar; R. Mohan; K. Mahalinganathan (Journal of Marine Systems, 2025)

Endocrine disrupting phenolic plasticizers in the Bay of Bengal coastal waters, India: Occurrence, Distribution and Environmental Risk Assessment - Gayathri R. Chandran; Arun Elaiyaraja; Aditya Mohan Menon; Vijayakumar Bommuraj; Perumal Santhanam; Ramaswamy Babu Rajendran (Environmental Pollution, 2025)

Arsenic in Aquatic Ecosystems: Sources, Risks, Remediation, and Governance in India with Respect to Global Significance - Shailendra Mohan Raut; Kamal Sarma; Dilip H. Lataye; Saurav Kumar; Suryakant Bajirao Tarate; Vikash K. Sonu; Upendra R. Darla; S. P. Shukla; Indu Shekhar Singh; Ramesh Kumar Sahni; Sudhanshu Kumar; Pushpah Kumari Sharma; et al. (Water, Air, & Soil Pollution, 2025)

Physiological, Biochemical, and Molecular Responses During Grafting in Horticultural Crops - Narayan Lal; Vikas Ramteke; Garima Diwan; Pragya Singh; Nisha Sahu; Debashish Hota; Maneesha S.R.; Nirmal Kumar Meena; Kapil Mohan Sharma; Govind Balasaheb Shiurkar; Ganesh Maske; N. R. Rangare (Plant Molecular Biology Reporter, 2025)

Innovative augmentation techniques and optimized ANN model for imagined speech decoding in EEG-based BCI - Anand Mohan; R. S. Anand (Cognitive Neurodynamics, 2025)

Methods for precipitating plasma proteins for stable isotope analysis of elasmobranch blood - Alexander M. Rubin; Sunita R. Shah Walter; John A. Mohan; Aaron B. Carlisle (Journal of Experimental Marine Biology and Ecology, 2025)

Spatiotemporal urban growth dynamics and its interactions with transportation networks in an unplanned urban conglomeration using satellite imagery: A case study of Mumbai Metropolitan Region, India - Gopal R. Patil; Samarth Y. Bhatia; Manish Yadav; Krishna Mohan Buddhiraju; K. Venugopala Rao (Land Use Policy, 2025)

Three-component models for the detection of phytoplankton size classes in the Indian sector of the Southern Ocean: Insights into climate-driven community shifts - Sudarsana Rao Pandi; Sarat Chandra Tripathy; Carlos Rafael B. Mendes; R. Chandrasekhar Naik; Sunil Kumar Padhi; Aneesh A. Lotliker; Rahul Mohan (Journal of Marine Systems, 2025)

Europium MOFs-enabled fluorescent membranes with optimized flux, filtration, and fouling resistance for wastewater treatment: A strategy to probe MOF distribution in membranes - Gayathri Karthikeyan; Vidya Devadiga; Sakar Mohan; R. Geetha Balakrishna (Journal of Environmental Chemical Engineering, 2025)

Retraction notice to “Green waste immobilized Ag/Cu feather like Bi-matrix on garment dye decomposes and their bio-efficacy” [Environ. Res. 242 (2024) 117761] - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Karthikeyan perumal (Environmental Research, 2025)

The Role of Patient Education in Low Anterior Resection Syndrome: A Systematic Review - P. Tang; R. Tovel; H. Ong; David Proud; Adele Burgess; Eleanor Watson; Wui Yeat Chen; David Lam; Helen Mohan (Journal of Cancer Education, 2025)
Low anterior resection syndrome (LARS) is a significant complication after sphincter-preserving rectal cancer surgery and negatively impacts a patient’s quality of life. Treatment of LARS is multimodal, and many treatments require engagement from the patient. Understanding the complex array of treatment options and the potential additive effects of different therapies can be difficult. This systematic review aims to assess the role of patient education in treatment of LARS in colorectal cancer patients. A systematic literature search was conducted on PubMed, EMBASE and Ovid Medline according to the PRISMA guidelines for articles published from 1946 to October 2023 and registered with PROSPERO: 42,023,434,601. Studies that reported on clinical outcomes of patients with LARS that underwent any educational intervention were included for this review. Results from five publications including 368 patients with LARS were reviewed for analysis. Three interventions were delivered to symptomatic patients postoperatively and two to all patients who underwent low anterior resection preoperatively. Five trial protocols were also included for analysis, including three preoperative and two postoperative interventions Education interventions were often delivered alongside co-interventions such as medications and pelvic floor physiotherapy. Four studies reported improvement of mean LARS scores and quality of life measures related to the education intervention and associated co-interventions. Patient education has a positive impact towards improving functional outcomes in patients with LARS following resection for rectal cancer. In practice, it is often used in conjunction with other interventions. Determining optimal content and delivery methods is a target for future research.

Seasonal dynamics of dissolved and particulate organic carbon in nearshore waters of the Andaman Islands - P. M. Mohan; R. Karuna Kumari; N. V. H. K. Chari; Sai Elangovan S.; J. Joyson Joe Jeevamani; Mamidala Harikrishna Prasad; Supriyo Chakraborty; V. Sachithanandam (Frontiers in Marine Science, 2025)
This study investigates the seasonal and spatial variability of hydrochemical parameters and organic carbon pools between the South Andaman Islands (SAI) and North Andaman Islands (NAI) under contrasting monsoonal regimes. Seawater temperature (26.1 – 33.5°C) was consistently higher in SAI due to reef-associated stratification, while NAI exhibited greater variability. Salinity (25.2 – 35.9) and pH were more stable in SAI, whereas NAI showed lower values and higher variability driven by freshwater inputs from the Bay of Bengal river systems. Turbidity and dissolved inorganic nutrients (DIN, DIP, DSi) were significantly higher in NAI, reflecting strong terrestrial and riverine influence. Dissolved organic carbon (DOC; 103 – 772 µM) and particulate organic carbon (POC; 22 – 168 µM) concentrations were consistently higher in NAI, particularly during the spring intermonsoon (SIM) and northeast monsoon (NEM), while SAI exhibited lower but more variable concentrations linked to reef metabolism. Seasonal drivers included freshwater and terrestrial inputs enhancing DOC during SIM and NEM, and monsoon-induced mixing reducing concentrations during the southwest monsoon (SWM). POC levels were enriched in NAI throughout, whereas SAI showed greater variability related to reef-derived particulate cycling. The POC: DOC ratio (0.04 – 0.83) highlighted contrasting biogeochemical regimes, with NAI dominated by particulate-rich terrestrial inputs and SAI characterized by variable phytoplankton- and reef-driven processes. These findings emphasize the role of monsoonal forcing in shaping carbon dynamics across the Andaman Islands and the contrasting influence of terrestrial inputs in NAI versus reef-associated processes in SAI, with implications for regional carbon cycling and ecosystem functioning.

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Development of Mini Tractor Operated Hydraulic Powered Sugarcane Leaf De-trasher - A. P. Mohan Kumar; R. Kavitha; R. Thiyagarajan; A. Surendrakumar (Sugar Tech, 2025)

A novel report of Rhizoctonia solani AG-4 HG-I associated with damping-off and wilt of quinoa (Chenopodium quinoa) in India - D. Chethan; R. Chandana; Farooq Khan; B.S. Kavya; T. Tharana Poonacha; R. Karan; Akash Bevanur; R. Kruthika; K.S. Ashwini; Yerranagari Vani; S.R. Anand; A. Mohan Rao; et al. (Physiological and Molecular Plant Pathology, 2025)

Enhancement of genetic gain for early seedling vigor traits through marker-assisted pedigree selection in rice (Oryza sativa L.) - Sudhamani Kalluru; Issa Keerthi; Madhavilatha Kommana; D. M. Withanawasam; Eswarayya Ramireddy; D. Mohan Reddy; V. Umamahesh; Lakshminarayana R. Vemireddy (Physiology and Molecular Biology of Plants, 2025)

Effects of soil and climatic variables on earthworm community structure at altitude in the Himalayan forest ecosystem - Shakoor Ahmed; Naseer Hussain; R. S. Pandiya Rajan; Jatinder Mohan Julka; Nithyanandam Marimuthu (Community Ecology, 2025)

A Comprehensive Review on Ethnic Fermented Millet Food Products and its Applications: A Global Scenario - Mulukuri Naveena; R. Jagan Mohan; N. Baskaran; S. Vignesh (Current Food Science and Technology Reports, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evaluation of plasma bubbling assisted high-pressure processed green coffee bean extract: Yield, quality characterization and e-nose aroma profiling - B. Kamalapreetha; R. Anbarasan; R. Jagan Mohan; R. Mahendran (Food and Humanity, 2025)

Recent developments in the design of functional derivatives of edaravone and exploration of their antioxidant activities - R. Divya Mohan; Naveen V. Kulkarni (Molecular Diversity, 2025)

Retraction notice to “Rationally construction of 2D & 3D material on h-BN @ SnO2/TiO2 micro-sphere enables for photocatalytic debasement of textile cloth dyes in waste water treatment” [Environ. Res. 251-P2 (2024) 118728] - A. Vasantham; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Karthikeyan Perumal (Environmental Research, 2025)

Retraction notice to “Pyto-Architechture of Ag, Au and Ag–Au bi-metallic nanoparticles using waste orange peel extract for enable carcinogenic Congo red dye degradation” [Environ. Res. 242 (2024) 117625] - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Sakkarapalayam M. Mahalingam (Environmental Research, 2025)

Cognizance about sea water intrusion by chemical analysis in coastal aquifer of southeast coast of India - V. Baskaran; M. Sridharan; R. Saravanane; S. Mohan (International Journal of Energy and Water Resources, 2025)

Classification of Imagined Speech Signals Using Functional Connectivity Graphs and Machine Learning Models - Anand Mohan; R. S. Anand (Brain Topography, 2025)

Citrinin (CIT), a polyketide mycotoxin from a mangrove endophytic fungus Penicillium rubens EF 363 and its bioactive potential - M. R. Revathy; Anjali S. Mohan; Dhanya Kesavan; M. Dhaneesha; P. V. Santhini; Muralidharan Vanuopadath; Bipin G. Nair; Remington X. Poulin; T. P. Sajeevan; Rosamma Philip (Vegetos, 2025)

Retraction notice to “Valorization of food and kitchen waste: An integrated strategy adopted for the production of poly-3-hydroxybutyrate, bioethanol, pectinase and 2,3-butanediol” [Bioresour. Technol. 310 (2020) 123515] - Raveendran Sindhu; Athulya Manju; Pooja Mohan; Rajendran Omana Rajesh; Aravind Madhavan; K.B. Arun; Sulfath Hakkim Hazeena; Anju Mohandas; Swathi Ponnusamy Rajamani; Anoop Puthiyamadam; Parameswaran Binod; R. Reshmy (Bioresource Technology, 2025)

Phytophagous probiotic foods: Exploring the intersection of characteristics, quality implications, health benefits, and market dynamics - Alaa Kareem Niamah; Shayma Thyab Gddoa Al-Sahlany; Hussein Katai Abdul-Sada; Pawan Prabhakar; Soubhagya Tripathy; Basant Kumar Dadrwal; Smita Singh; Deepak Kumar Verma; Alok Kumar Gupta; Rakesh Mohan Shukla; Mamta Thakur; Ami R. Patel; et al. (Trends in Food Science & Technology, 2024)

Tasar Silkworm Pupae oil: A potential therapeutic and edible lipid source to mitigate the oxidative stress and cholesterol complications associated with diabetes - Devika Srivastava; Prashant Pandey; Deepak Kumar Tripathi; Jagat Pal Yadav; Bulbul Ali; Vandana Singh; Abhishek Verma; Akash Mishra; Dinesh Kumar; Abha Mishra; Paruvathanahalli Siddalingam Rajinikanth; Krishna Mohan Poluri; et al. (Food and Humanity, 2024)

High temperature stress induced changes in physiological, biochemical, hormonal and gene expression patterns in contrasting tomato genotypes - Vijayakumar Amrutha; Mohan Reshma; R. V. Manju; K. N. Anith; Pratheesh P. Gopinath; S. Sarada; R. Beena (Plant Physiology Reports, 2024)

Physiological Responses to Acute Heat Stress in Rohu, Labeo rohita: Insights from Liver Proteomics - Mohan R. Badhe; Priyanka Das; Sonalina Sahoo; Anirban Paul; Pramoda Kumar Sahoo; R. Rajendra Kumar Reddy; Amol R. Suryawanshi; Priyanka C. Nandanpawar; Kanta Das Mahapatra; Naresh S. Nagpure; Mukunda Goswami; Jyotirmaya Mohanty (Marine Biotechnology, 2024)

Remote Sensing-Based Ecosystem Monitoring and Disaster Management in Urban Environments Using Machine Learnings - M. Mohan; Anila Macharla; Parthasarathi P.; Bediga Sharan; A. Nageswaran; Balajee R. M. (Remote Sensing in Earth Systems Sciences, 2024)

Carbothermally synthesized, lignin biochar-based, embedded and surface deposited nano zero-valent iron composites: Comparative material characterization, selective gas adsorption and nitroaromatics remediation - Yasmitha A. Alahakoon; Shine C. Wilson; Chathuri Peiris; Yohara K. Ranasinghe; Sameera R. Gunatilake; Xuefeng Zhang; Todd E. Mlsna; Upul Kumarasinghe; M.Infas H Mohideen; Upendar Reddy Gandra; Anish Mathai Varghese; Georgios N. Karanikolos; et al. (Colloids and Surfaces C: Environmental Aspects, 2024)

Ultrasonic Assisted Synthesis of CuFe2O4-Ag infused Gum Hydrogels Nanocomposite for photocatalytic Degradation of Organic Dye from Wastewater - Meenu; Pratibha Sharma; Roli Purwar; Navita Sharma; Pooja Rawat; Seema R. Pathak; Atul Thakur; Hyunook Kim; Monu Verma; Sudip Majumder; Chandra Mohan Srivastava (Water, Air, & Soil Pollution, 2024)

P19-93 Using high throughput screening asapreliminary tool for predicting environmental risk of chemicals - R. Hirawat; V. Mohan (Toxicology Letters, 2024)

Effect of neighbourhood and its configurations on urban growth prediction of an unplanned metropolitan region - Samarth Y. Bhatia; Kirtesh Gadiya; Gopal R. Patil; Buddhiraju Krishna Mohan (Applied Geomatics, 2024)

Elevated Complement Activation Fragments and C1q-Binding Circulating Immune Complexes in Varied Phases of Chikungunya Virus Infection - Rewati Kasbe; Anuradha S. Tripathy; Mohan R. Wani; Jayati Mullick (Current Microbiology, 2024)

Short-term time-series observations of phytoplankton light-absorption and productivity in Prydz Bay, coastal Antarctica - Sarat C. Tripathy; Anvita U. Kerkar; P. Sabu; Sunil K. Padhi; Sudarsana R. Pandi; Amit Sarkar; Bhaskar V. Parli; Rahul Mohan (Frontiers in Marine Science, 2024)
The optical characteristics of coastal Antarctic waters exhibit complexity due to the dynamic hydrography influenced by meltwater intrusion, which alters nutrient levels, thermohaline structure, and optically active substances (OAS) regimes. Studies on bio-optical variability and its implications on phytoplankton productivity (PP) are scanty in coastal polar regions. On this backdrop, time-series measurements (72 h at 6 h intervals) of bio-optical properties such as phytoplankton biomass (chlorophyll-a), absorption (a ph ), and total suspended matter (TSM) concurrently with PP were measured to understand their interplay and variability in relation to the ambient physicochemical settings in the under-sampled Prydz Bay, coastal Antarctica. Our findings revealed thermohaline stratification within the bay, likely attributed to the inflow of less saline meltwater from nearby glaciers and minimal wind activity. The consistent presence of sub-surface chlorophyll maximum (SCM) beneath the stratified layer underscored the light-acclimatization response of shade-adapted phytoplankton. Surface waters exhibited higher TSM compared to deeper layers, indicating glacial melt influence, while the depth of the sunlit layer remained relatively stable, suggesting limited water mass movement and/or variability in OAS at the study site. An inverse relation between chlorophyll-a and chlorophyll-a-specific phytoplankton light absorption (a* ph (λ)) manifested ‘pigment package effect’ within the prevailing phytoplankton community, implying reduced light-absorption efficiency and consequent lower PP. Compared to chlorophyll-a, the phytoplankton light absorption (a ph (λ)) emerged as a better proxy for explaining PP variability. Nutrient availability was not limiting, which was conducive to micro (large) phytoplankton growth. Classification of phytoplankton size classes (micro, nano, and pico) based on the B/R ratio (a ph at Blue (443 nm)/Red (676 nm) region) confirmed the dominance of larger (micro) phytoplankton that are more susceptible to package effect, thus have implications on reduced PP potential of this polar marine ecosystem.

Comprehensive mathematical model for efficient and robust control of irrigation canals - Rajani Pandey; G R Jayanth; M.S Mohan Kumar (Environmental Modelling & Software, 2024)

Manifestation of UiO-66-Zr MOF-enabled photocatalytic membranes for successive separation and degradation of dye mixtures in water remediation - K. Gayathri; K. Vinothkumar; Sakar Mohan; R. Geetha Balakrishna (Journal of Environmental Chemical Engineering, 2024)

RETRACTED: Rationally construction of 2D & 3D material on h-BN @ SnO2/TiO2 micro-sphere enables for photocatalytic debasement of textile cloth dyes in waste water treatment - A. Vasantham; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Karthikeyan Perumal (Environmental Research, 2024)

Improved photocatalytic degradation of organic pollutants using green synthesized ZnO and Ni@ZnO NPs for environmental applications - N.S. Mohan; S. Bhuvaneswari; R. Anitha; V. Vijayalakshmi (Environmental Nanotechnology, Monitoring & Management, 2024)

Linum usitatissimum mediated green synthesis of Cu3V2O8 nanoparticles and its photocatalytic activity studies - Divya R. Basavannavar; Kunal Mohan Mishra; Adheena Biju; E. Vinay kumar; J.R. Naveen Kumar; B.M. Praveen; G. Nagaraju (Environmental Nanotechnology, Monitoring & Management, 2024)

Antimicrobial susceptibility of mastitis pathogens isolated from North American dairy cattle, 2011-2022 - Michael T. Sweeney; Lacie Gunnett; Dipu Mohan Kumar; Bryce L. Lunt; Véronique Moulin; Michele Barrett; Abhijit Gurjar; Elizabeth Doré; Juan R. Pedraza; Don Bade; Chandra Machin (Veterinary Microbiology, 2024)

Geochemical partitioning of sediment-bound phosphorous in Thrissur Kole Wetlands, Southwest India: Status of bioavailability and trophic state - P. V. Vidya; S. Rajathy; C. S. Ratheesh Kumar; S. K. Maneesh Kumar; K. B. Akhilesh; R. Mohan; A. Sudha (International Journal of Environmental Science and Technology, 2024)

An improvement in water stress tolerance in rice by altering morpho-physiological and biochemical mechanisms using root colonizing endophyte Piriformospora indica - S. Lekshmi Mohan; R. Beena; M. Joy (Vegetos, 2024)

Exploring bacterial diversity in Arctic fjord sediments: a 16S rRNA–based metabarcoding portrait - Bhavya Kachiprath; Solly Solomon; Jayanath Gopi; P. R. Jayachandran; Jabir Thajudeen; Manomi Sarasan; Anjali S. Mohan; Jayesh Puthumana; E. R. Chaithanya; Rosamma Philip (Brazilian Journal of Microbiology, 2024)

RETRACTED: Green waste immobilized Ag/Cu feather like Bi-matrix on garment dye decomposes and their bio-efficacy - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Karthikeyan perumal (Environmental Research, 2024)

RETRACTED: Pyto-Architechture of Ag, Au and Ag–Au bi-metallic nanoparticles using waste orange peel extract for enable carcinogenic Congo red dye degradation - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Sakkarapalayam M. Mahalingam (Environmental Research, 2024)

Biodegradation of naphthalene – Ecofriendly approach for soil pollution mitigation - Srivalli Thimmarayan; Harshavardhan Mohan; Gaddapara Manasa; Karthi Natesan; Shanmugam Mahendran; Pavithra Muthukumar Sathya; Byung-Taek Oh; R. Ravi Kumar; Rangasamy Sigamani Gandhimathi; Arul Jayaprakash; Kamala-Kannan Seralathan (Environmental Research, 2024)

Insights into the characterization and therapeutic potential of Tasar silkworm pupal oil - Devika Srivastava; Deepak Kumar Tripathi; Vandana Singh; Krishna Mohan Poluri; Venkatesh Kumar R (Biocatalysis and Agricultural Biotechnology, 2024)

Efficacy of surfactants in the sustainable restoration of the geotechnical properties of diesel-contaminated soil - A. Kumar; D. Mohan; B. R. Paramkusam; A. P. Singh (International Journal of Environmental Science and Technology, 2024)

Insights into vertebral band pair deposition rate in the juvenile common thresher shark ( Alopias vulpinus ) in the northeastern Pacific Ocean - Luka N. Spear; Suzanne Kohin; John A. Mohan; R. J. David Wells (Journal of Fish Biology, 2024)
Validation of band pair deposition rates in elasmobranch vertebrae is essential for accurate age estimation using band pair counting techniques. We present a validation study of the vertebral band pair deposition rate for juvenile common thresher sharks Alopias vulpinus in the northeastern Pacific Ocean (NEPO) using tag and recapture with oxytetracycline (OTC) injection. A total of 14 juvenile A . vulpinus marked with OTC from 1998 through 2013 were recaptured with times at liberty ranging from 1.08 to 3.81 years with an average of 2.14 years (±0.97 years standard deviation, SD). Shark size ranged from 80 to 128 cm fork length (LF) at the time of OTC injection and from 112 to 168 cm LF for those measured at recapture. The slopes of the relationships between band pairs post OTC and years at liberty for each reader ranged from 0.84 to 0.95, slightly lower than the 1.0 slope expected from annual band pair formation. These findings preliminarily support previous age and growth assumptions based on a one band pair per year deposition rate. However, high variation in band pair deposition rates between samples, coupled with regression slopes falling just under one band pair per year, indicates that further investigation is needed to refine band pair deposition rate estimates.

Characterization of a Lipopolysaccharide- and Beta-1,3-Glucan Binding Protein (LGBP) from the Hepatopancreas of Freshwater Prawn, Macrobrachium rosenbergii, Possessing Lectin-Like Activity - Sonalina Sahoo; Mohan R. Badhe; Anirban Paul; Pramoda Kumar Sahoo; Amol R. Suryawanshi; Debabrata Panda; Bindu R. Pillai; Bharat Bhusan Patnaik; Jyotirmaya Mohanty (Probiotics and Antimicrobial Proteins, 2023)

On the simulations of latent heat flux over the Indian Ocean in CMIP6 models - Soumya Mohan; R. D. Ruchith (Climate Dynamics, 2023)

Influence of quantity, quality, horizontal and vertical distribution of ground control points on the positional accuracy of UAV survey - Dharshan Shylesh D S; Manikandan N; Sivasankar S; Surendran D; Jaganathan R; Mohan G (Applied Geomatics, 2023)

Remote sensing-based assessment of mangrove ecosystems in the Gulf Cooperation Council countries: a systematic review - Marcela Rondon; Ewane Basil Ewane; Meshal M. Abdullah; Michael S. Watt; Austin Blanton; Ammar Abulibdeh; John A. Burt; Kerrylee Rogers; Tarig Ali; Ruth Reef; Rabi Mohtar; Frida Sidik; et al. (Frontiers in Marine Science, 2023)
Mangrove forests in the Gulf Cooperation Council (GCC) countries are facing multiple threats from natural and anthropogenic-driven land use change stressors, contributing to altered ecosystem conditions. Remote sensing tools can be used to monitor mangroves, measure mangrove forest-and-tree-level attributes and vegetation indices at different spatial and temporal scales that allow a detailed and comprehensive understanding of these important ecosystems. Using a systematic literature approach, we reviewed 58 remote sensing-based mangrove assessment articles published from 2010 through 2022. The main objectives of the study were to examine the extent of mangrove distribution and cover, and the remotely sensed data sources used to assess mangrove forest/tree attributes. The key importance of and threats to mangroves that were specific to the region were also examined. Mangrove distribution and cover were mainly estimated from satellite images (75.2%), using NDVI (Normalized Difference Vegetation Index) derived from Landsat (73.3%), IKONOS (15%), Sentinel (11.7%), WorldView (10%), QuickBird (8.3%), SPOT-5 (6.7%), MODIS (5%) and others (5%) such as PlanetScope. Remotely sensed data from aerial photographs/images (6.7%), LiDAR (Light Detection and Ranging) (5%) and UAV (Unmanned Aerial Vehicles)/Drones (3.3%) were the least used. Mangrove cover decreased in Saudi Arabia, Oman, Bahrain, and Kuwait between 1996 and 2020. However, mangrove cover increased appreciably in Qatar and remained relatively stable for the United Arab Emirates (UAE) over the same period, which was attributed to government conservation initiatives toward expanding mangrove afforestation and restoration through direct seeding and seedling planting. The reported country-level mangrove distribution and cover change results varied between studies due to the lack of a standardized methodology, differences in satellite imagery resolution and classification approaches used. There is a need for UAV-LiDAR ground truthing to validate country-and-local-level satellite data. Urban development-driven coastal land reclamation and pollution, climate change-driven temperature and sea level rise, drought and hypersalinity from extreme evaporation are serious threats to mangrove ecosystems. Thus, we encourage the prioritization of mangrove conservation and restoration schemes to support the achievement of related UN Sustainable Development Goals (13 climate action, 14 life below water, and 15 life on land) in the GCC countries.

Latent heat flux variability over the tropical Indian Ocean - Soumya Mohan; R. D. Ruchith; S. Rahul; P. R. Shanas (International Journal of Climatology, 2023)
The seasonal evolution and interannual variability of latent heat flux (LHF) over the tropical Indian Ocean (TIO) region is examined for the period 1980–2019. The seasonal distribution of LHF is dominated by the winter pattern of each hemisphere in the TIO. Climatologically high LHF is mostly confined to the Arabian Sea and Bay of Bengal regions in the north Indian Ocean and the zonal belt between 10 o S and 25 o S in the south Indian Ocean. Warm and cold phases of El‐Niño Southern Oscillation, Indian Ocean Dipole (IOD), and their co‐occurrence events leave distinct LHF signatures over the TIO. The LHF anomalies during these events are more profound than pure events with enhanced latent heat loss when the La Niña and negative IOD events coincide. The LHF anomalies associated with the wind‐evaporation‐SST feedback is prominent when positive IOD co‐occur with the El‐Niño event. Both the vertical humidity gradient and wind speed changes play substantial roles in driving LHF anomalies during the co‐occurring events of NIOD and La Niña.

Effect of acute cold exposure on cardiac mitochondrial function: role of sirtuins - Mithra. S. Mohan; S. S. Aswani; N. S. Aparna; P. T. Boban; P. R. Sudhakaran; K. Saja (Molecular and Cellular Biochemistry, 2023)

Sex influences elemental variation in the mineralized vertebrae cartilage of round stingray (Urobatis halleri) - Bethany E. Brodbeck; Kady Lyons; Nathan R. Miller; John A. Mohan (Marine Biology, 2023)
The elemental composition of mineralized vertebral cartilage has proven useful for reconstructing the movement and environmental history of elasmobranchs. However, the effects of intrinsic and extrinsic factors on vertebral chemistry have not been well explored, making meaningful interpretations of results difficult. This study quantified trace element incorporation along the corpus calcareum of 116 Round Stingray ( Urobatis halleri ) vertebrae and explored the influence of intrinsic (i.e., sex) and extrinsic (i.e., location and year) factors on vertebral edge chemical variations. We quantified eight element/Ca ratios (Li/Ca, Mg/Ca, Mn/Ca, Co/Ca, Cu/Ca, Zn/Ca, Sr/Ca, Ba/Ca) by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Behavioral sexual segregation by Round Stingrays explained differences found in Mn/Ca, Zn/Ca, Sr/Ca, and Ba/Ca ratios. Higher vertebral Mn/Ca and Zn/Ca in females likely originate from the use of salt marsh habitats as a refuge as well as higher reproductive hormone concentrations during gestation, respectively. Female and male Round Stingrays were also found to have an inverse relationship between Sr/Ca and Ba/Ca, likely due to environmental differences (e.g., temperature) between their sexually segregated habitats. This study demonstrates how multielement signatures in vertebral cartilage may improve understanding of habitat use and migration throughout life and advances the development of biomineral usage as an environmental proxy in elasmobranchs.

Tilapia aquaculture, emerging diseases, and the roles of the skin microbiomes in health and disease - Sanjit Chandra Debnath; Jamie McMurtrie; Ben Temperton; Jérôme Delamare-Deboutteville; Chadag Vishnumurthy Mohan; Charles R. Tyler (Aquaculture International, 2023)
Aquaculture is playing an increasingly important role in global food security, especially for low-income and food-deficit countries. The majority of aquaculture production occurs in freshwater earthen ponds and tilapia has quickly become one of the most widely adopted culture species in these systems. Tilapia are now farmed in over 140 countries facilitated by their ease of production, adaptability to a wide range of environmental conditions, fast growth, and high nutritional value. Typically, tilapia have been considered a hardy, disease resilient species; however, the disease is increasing with subsequent threats to the industry as their production is intensified. In this review, we discuss tilapia production, with a focus on Bangladesh as one of the top producing countries, and highlight the problems associated with disease and treatment approaches for them, including the misuse of antimicrobials. We address a key missing component in understanding health and disease processes for sustainable production in aquaculture, specifically the role played by the microbiome. Here we examine the importance of the microbiome in supporting health, focused on the symbiotic microbial community of the fish skin mucosal surface, the abiotic and biotic factors that influence the microbiome, and the shifts that are associated with diseased states. We also identify conserved taxa of skin microbiomes that may be used as indicators of health status for tilapia offering new opportunities to mitigate and manage the disease and optimize environmental growing conditions and farming practices.

Guillain Barre Syndrome as a Complication of Infections Including COVID-19: a Review - Shruti V. Kurup; Pratiksha M. Patil; Sonam S. Atkari; Sakshi R. Divate; Baban S. Thawkar; Mohan K. Kale (Current Pharmacology Reports, 2023)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Flexible, symmetric supercapacitor using self-stabilized dispersion-polymerised polyaniline/V2O5 hybrid electrodes - R. Rohith; Anandhu Thejas Prasannakumar; V. Manju; Ranjini R. Mohan; Sreekanth J. Varma (Chemical Engineering Journal, 2023)

A novel biomass derived activated carbon mediated AC@ZnO/NiO bifunctional nanocatalyst to produce high-quality biodiesel from dairy industry waste oil: CI engine performance and emission - Basir Maleki; Yatish Kalanakoppal Venkatesh; S. Siamak Ashraf Talesh; Hossein Esmaeili; Sakar Mohan; Geetha R. Balakrishna (Chemical Engineering Journal, 2023)

Special Issue: Geostatistics Toronto 2021 - Sebastian Avalos; Julian M. Ortiz; R. Mohan Srivastava (Mathematical Geosciences, 2023)

Correction: Concurrent Assessment of Oxidative Stress and MT-ATP6 Gene Profiling to Facilitate Diagnosis of Autism Spectrum Disorder (ASD) in Tamil Nadu Population - Balachandar Vellingiri; Dhivya Venkatesan; Mahalaxmi Iyer; Gomathi Mohan; Padmavathi Krishnan; Krothapalli Sai Krishna; Sangeetha R; Arul Narayanasamy; Abilash Valsala Gopalakrishnan; Nachimuthu Senthil Kumar; Mohana Devi Subramaniam (Journal of Molecular Neuroscience, 2023)

Investigating underground water salinity in east coastline of Tamil Nadu, India and improving its quality through solar assisted desalination - V. Kanchana; P. Manoj Kumar; P. Suresh Kumar; I. Kathir; R. Thirumalai; D. Priya; R. Puviarasi; M. Mohan Prasad (Urban Climate, 2023)

Assessment of underground water quality and water quality index across the Noyyal River basin of Tirupur District in South India - N. Krishnamoorthy; R. Thirumalai; M. Lenin Sundar; M. Anusuya; P. Manoj Kumar; E. Hemalatha; M. Mohan Prasad; Neha Munjal (Urban Climate, 2023)

Concurrent Assessment of Oxidative Stress and MT-ATP6 Gene Profiling to Facilitate Diagnosis of Autism Spectrum Disorder (ASD) in Tamil Nadu Population - Balachandar Vellingiri; Dhivya Venkatesan; Mahalaxmi Iyer; Gomathi Mohan; Padmavathi Krishnan; Krothapalli Sai Krishna; Sangeetha R; Arul Narayanasamy; Abilash Valsala Gopalakrishnan; Nachimuthu Senthil Kumar; Mohana Devi Subramaniam (Journal of Molecular Neuroscience, 2023)

Infestation, distribution and diversity indices of bruchid species on edible stored pulses in India - Revanasidda Aidbhavi; Murali Mohan K; Soren K R; Sanjay M Bandi; Ranjitha M R; Kodandaram M H (Journal of Stored Products Research, 2023)

Petrogenesis of Meso-Neoarchean granitoids from the Chitradurga Greenstone Belt: Implications on crustal growth and reworking of the Dharwar Craton, southern India - M. Ram Mohan; Neal J. McNaughton; D. Srinivasa Sarma; M. Rajamanickam; Ian R. Fletcher; Simon A. Wilde; Birger Rasmussen; Bryan Krapež; S. Balakrishnan (Journal of Asian Earth Sciences, 2023)

Identification of genomic regions governing moisture and heat stress tolerance employing association mapping in rice (Oryza sativa L.) - Madhavilatha Kommana; D. Mohan Reddy; K. Amarnath; M. Vinod Kumar Naik; D. M. Withanawasam; Reddyyamini Bommisetty; K. Maneesha; M. Bhargavi; Aparna Eragam; B. V. Bhaskara Reddy; P. Sudhakar; Lalam Krishna; et al. (Molecular Biology Reports, 2023)

Inferring habitat use of the Pacific White Shark using vertebral chemistry - John A. Mohan; Alfonsina E. Romo-Curiel; Sharon Z. Herzka; R. J. David Wells; Nathan R. Miller; Oscar Sosa-Nishizaki; Emiliano García-Rodríguez (Frontiers in Marine Science, 2023)
The conservation and management of highly migratory sharks relies on understanding age-related movements and nursery habitat utilization. We reconstructed the habitat use and migratory history of young White Sharks ( Carcharodon carcharias ), a highly protected species, by utilizing natural chemical tracers (element:Ca ratios and stable isotope analysis, SIA) in vertebral cartilage growth bands. Two nursery areas in the northeastern Pacific are known, but migration patterns of immature White Sharks within the Gulf of California (GC) and natal philopatry are poorly understood. Vertebrae from coastal Mexican artisanal fisheries off central Baja California in the Pacific (12 neonates and juveniles; 139-280 cm total length) and the GC (3 subadults; 289-355 cm TL) were analyzed to characterize (1) trophic histories from collagen δ 13 C and δ 15 N values, and (2) in utero patterns and post-birth environmental histories from element:Ca time-series. Mean δ 15 N values from vertebral edges of GC sharks, representing the most recent feeding, was +5‰ higher than in the Pacific, reflecting the intense denitrification that permeates the regional food web and supporting SIA as tracers of migration between regions. A subadult from the GC likely resided within the system throughout its life, and two subadults migrated into the GC. Most neonate and juvenile sharks caught in the Pacific had SIA that did not overlap with those of the GC, but a single subadult likely migrated to the GC. Element:Ca ratios displayed ontogenetic trends, with Li:Ca, Zn:Ca, and Ba:Ca significantly higher before the birth mark in sharks captured in the GC. Edge values were significantly higher in Zn:Ca and Ba:Ca in the GC compared to the Pacific, suggesting elemental ratios may serve as tracers of migration between regions. Subadult sharks collected from GC displayed elevated maternal Zn:Ca and Ba:Ca, suggesting mothers may have resided in the GC for an extensive period pre-birth. Some White Sharks may reside within the GC from birth until at least the subadult stage (ca. 3 m TL), and there may be an unidentified nursery. Chemical tracers, coupled with genomic and tagging studies, should improve understanding of the importance of the GC to White Shark populations in the northeast Pacific.

Facile construction of cost-effective zinc-aluminium polymeric framework for efficient removal of selective both drug and dye from an aqueous medium - R. Mohan Raj; Sivarasan Ganesan; S. Suganthi; S. Vignesh; Ashraf Atef Hatamleh; Bassam Khalid Alnafisi; Raja Venkatesan; V. Raj; Huang-Mu Lo (Chemosphere, 2023)

Non‐antibiotic approaches to combat motile Aeromonas infections in aquaculture: Current state of knowledge and future perspectives - Le Thanh Dien; Thao Phuong Huynh Ngo; Thao V. Nguyen; Pattanapon Kayansamruaj; Krishna R. Salin; Chadag Vishnumurthy Mohan; Channarong Rodkhum; Ha Thanh Dong (Reviews in Aquaculture, 2023)
Inland aquaculture contributed by three major fish groups, including carps, tilapias, and catfish plays a vital role in global food security and nutrition, particularly in low and middle‐income countries. However, the sustainable development of this sector is hampered by disease epidemics, especially those caused by bacteria such as Aeromonas species. At least eight pathogenic motile Aeromonas species ( A. hydrophila , A. veronii , A. jandaei , A. caviae , A. sobria , A. bestiarum , A. dhakensis and A. schubertii ) have been reported in aquaculture with some causing up to 100% mortality during disease outbreaks. Simultaneously, emerging multidrug‐resistant Aeromonas due to a long‐inappropriate use of antibiotics is alarming and highlights a global public health concern and negative socioeconomic impacts. Here, we provide a comprehensive overview of motile Aeromonas infections, antibiotic use and antimicrobial resistance of Aeromonas species . This contribution also highlights the non‐antibiotic approaches (the solutions for preventing or treating of bacterial diseases without resorting to antibiotic use) to control motile Aeromonas infections. In addition to the current state of knowledge and limitations of each prophylaxis/therapy, perspectives for future research are discussed critically, including oral/immersion multivalent vaccines, microencapsulated synbiotics, exogenous metabolites, and novel lytic bacteriophage cocktails. Some emerging applicable nanotechnology themes such as nanovaccines, nanobioactive compounds, and nanobubbles are also included in this review. In summary, combating motile Aeromonas infections in aquaculture, including multidrug‐resistant aeromonads, as well as other bacterial diseases, is a lengthy battle that requires a strategic combination of multiple non‐antibiotic approaches coherent with the One Health philosophy.

Identification of molecular markers and putative candidate genes associated with early seedling vigour traits in rice (Oryza sativa L.) - Sudhamani Kalluru; Lakshminarayana R. Vemireddy; Eswarayya Ramireddy; D. Mohan Reddy; V. Umamahesh (Brazilian Journal of Botany, 2022)

Evaluation of five high-resolution global model rainfall forecasts over India during monsoon 2020 - Raghavendra Ashrit; Mohan S Thota; Anumeha Dube; Kondapalli Niranjan Kumar; S Karunasagar; Sushant Kumar; Harvir Singh; Rajasekhar Meka; R Phani Murali Krishna; Ashis K Mitra (Journal of Earth System Science, 2022)

Wheat quality index: new holistic approach to identify quality superior genotypes - Devinder Mohan; R. Sendhil; Om Prakash Gupta; Vanita Pandey; Gopalareddy Krishnappa; Gyanendra Pratap Singh (Cereal Research Communications, 2022)

Recycling of platinum group metals from exhausted petroleum and automobile catalysts using bioleaching approach: a critical review on potential, challenges, and outlook - Ashish Pathak; Hanadi Al-Sheeha; R. Navvamani; Richa Kothari; Meena Marafi; Mohan S. Rana (Reviews in Environmental Science and Bio/Technology, 2022)

Nutritional Crispy from Fish Scales for Human Diet - K. R. Sreelakshmi; Rehana Raj; S. Remya; V. A. Minimol; C. O. Mohan; George Ninan (Journal of Aquatic Food Product Technology, 2022)

Pyramiding of drought adaptive traits and development of doubled haploids in the traits pyramided rice (Oryza sativa L.) - Kavita Kotyal; Chaitanya Ghalagi; M. R. Namratha; Basavaiah Mohan Raju (Plant Physiology Reports, 2022)

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Mechanism underpinning the sharpening of orientation and spatial frequency selectivities in the tree shrew (Tupaia belangeri) primary visual cortex - Yamni S. Mohan; Sivaram Viswanathan; Jaikishan Jayakumar; Errol K. J. Lloyd; Trichur R. Vidyasagar (Brain Structure and Function, 2022)

Vertical distribution of PM10 and PM2.5 emission sources and chemical composition during winter period in Delhi city - R. Shanmuga Priyan; Anju Elizbath Peter; Jyothi S. Menon; Mohan George; S. M. Shiva Nagendra; Mukesh Khare (Air Quality, Atmosphere & Health, 2022)

Towards holistic technology solution to chromite ore processing residue (COPR) challenge; global issue: review and analysis - R. Mohan; L. Deevakar; V. Sivakumar (International Journal of Environmental Science and Technology, 2022)

Why Indian Scientific Contributions do not Fetch Nobel Prize - Velayudhan Mohan Kumar; Seithikurippu R. Pandi-Perumal (Sleep and Vigilance, 2021)

A novel four-step feature selection technique for diabetic retinopathy grading - N. Jagan Mohan; R. Murugan; Tripti Goel; Seyedali Mirjalili; Parthapratim Roy (Physical and Engineering Sciences in Medicine, 2021)

Occurrence of the supposedly endemic Australian azooxanthellate coral Astrangia woodsi Wells, 1955 in the eastern Arabian Sea - Divya Viswambharan; K. R. Sreenath; S. Jasmine; K. K. Joshi; C. R. Sreeraj; Smruthu Mohan; Prathibha Rohit (Marine Biodiversity, 2021)

Biomass and vegetation carbon stock in mangrove forests of the Andaman Islands, India - P. Ragavan; Sanjeev Kumar; K. Kathiresan; P. M. Mohan; R. S. C. Jayaraj; K. Ravichandaran; T. S. Rana (Hydrobiologia, 2021)

Belowground community turnover accelerates the decomposition of standing dead wood - Mark A. Bradford; Daniel S. Maynard; Thomas W. Crowther; Paul T. Frankson; Jacqueline E. Mohan; Corinna Steinrueck; G. F. (Ciska) Veen; Joshua R. King; Robert J. Warren (Ecology, 2021)
Standing dead trees (snags) decompose more slowly than downed dead wood and provide critical habitat for many species. The rate at which snags fall therefore influences forest carbon dynamics and biodiversity. Fall rates correlate strongly with mean annual temperature, presumably because warmer climates facilitate faster wood decomposition and hence degradation of the structural stability of standing wood. These faster decomposition rates coincide with turnover from fungal‐dominated wood decomposer communities in cooler forests to codomination by fungi and termites in warmer regions. A key question for projecting forest dynamics is therefore whether temperature effects on wood decomposition arise primarily because warmer conditions facilitate faster decomposer metabolism, or are also influenced indirectly by belowground community turnover (e.g., termites exert additional influence beyond fungal‐plus‐bacterial mediated decomposition). To test between these possibilities, we simulate standing dead trees with untreated wooden posts and follow them in the field across 5 yr at 12 sites, before measuring buried, soil–air interface and aerial post sections to quantify wood decomposition and organism activities. High termite activities at the warmer sites are associated with rates of postfall that are three times higher than at the cooler sites. Termites primarily consume buried wood, with decomposition rates greatest where termite activities are highest. However, where higher microbial and termite activities co‐occur, they appear to compensate for one another first, and then to slow decomposition rates at their highest activities, suggestive of interference competition. If the range of microbial and termite codomination of wood decomposer communities expands under climate warming, our data suggest that expansion will accelerate snag fall with consequent effects on forest carbon cycling and biodiversity in forests previously dominated by microbial decomposers.

Ensuring the adaptive potential of Coastal wetlands of India- the need of the hour for sustainable management - P. Ragavan; K. Kathiresan; P. M. Mohan; K. Ravichandran; R. S. C. Jayaraj; T. S. Rana (Wetlands Ecology and Management, 2021)

Multi-drug resistant (MDR), extended spectrum beta-lactamase (ESBL) producing and carbapenem resistant Escherichia coli in rescued Sloth bears (Melursus ursinus), India - O. R. VinodhKumar; M. Karikalan; S. Ilayaraja; Arun A. Sha; B. R. Singh; D. K. Sinha; S. Chandra Mohan; B. S. Pruthvishree; A. M. Pawde; A. K. Sharma (Veterinary Research Communications, 2021)

Eliciting heavy metal contamination on selected native organisms from Cochin estuary using contemporary biomarker approach - N D Don Xavier; S Bijoy Nandan; P R Jayachandran; K V Neethu; D Mohan; S R Marigoudar (Journal of Earth System Science, 2021)

IL-3 inhibits rat osteoclast differentiation induced by TNF-α and other pro-osteoclastogenic cytokines - Vikrant Piprode; Kanupriya Singh; Anil Kumar; Snehal R. Joshi; Mohan R. Wani (Journal of Biosciences, 2021)

Ontogenetic Patterns of Elemental Tracers in the Vertebrae Cartilage of Coastal and Oceanic Sharks - Mariah C. Livernois; John A. Mohan; Thomas C. TinHan; Travis M. Richards; Brett J. Falterman; Nathan R. Miller; R. J. David Wells (Frontiers in Marine Science, 2021)
As predators, coastal and oceanic sharks play critical roles in shaping ecosystem structure and function, but most shark species are highly susceptible to population declines. Effective management of vulnerable shark populations requires knowledge of species-specific movement and habitat use patterns. Since sharks are often highly mobile and long-lived, tracking their habitat use patterns over large spatiotemporal scales is challenging. However, the analysis of elemental tracers in vertebral cartilage can describe a continuous record of the life history of an individual from birth to death. This study examined trace elements (Li, Mg, Mn, Zn, Sr, and Ba) along vertebral transects of five shark species with unique life histories. From most freshwater-associated to most oceanic, these species include Bull Sharks ( Carcharhinus leucas ), Bonnethead Sharks ( Sphyrna tiburo ), Blacktip Sharks ( Carcharhinus limbatus ), Spinner Sharks ( Carcharhinus brevipinna ), and Shortfin Mako Sharks ( Isurus oxyrinchus ). Element concentrations were compared across life stages (young-of-the-year, early juvenile, late juvenile, and adult) to infer species-specific ontogenetic patterns of habitat use and movement. Many of the observed elemental patterns could be explained by known life history traits: C. leucas exhibited clear ontogenetic changes in elemental composition matching expected changes in their use of freshwater habitats over time. S. tiburo elemental composition did not differ across ontogeny, suggesting residence in estuarine/coastal regions. The patterns of elemental composition were strikingly similar between C. brevipinna and C. limbatus , suggesting they co-occur in similar habitats across ontogeny. I. oxyrinchus elemental composition was stable over time, but some ontogenetic shifts occurred that may be due to changes in migration patterns with maturation. The results presented in this study enhance our understanding of the habitat use and movement patterns of coastal and oceanic sharks, and highlights the applicability of vertebral chemistry as a tool for characterizing shark life history traits.

Semaphorin3F Drives Dendritic Spine Pruning Through Rho-GTPase Signaling - Bryce W. Duncan; Vishwa Mohan; Sarah D. Wade; Young Truong; Alexander Kampov-Polevoi; Brenda R. Temple; Patricia F. Maness (Molecular Neurobiology, 2021)

Green mussel (Perna viridis L.) farming in India: an analysis of major growth milestones, recent decline due to disease incidence, and prospects for revival - Shinoj Parappurathu; N. K. Sanil; P. K. Asokan; S. R. Krupesha Sharma; M. A. Pradeep; Shelton Padua; Suja Gangadharan; Gishnu Mohan; Prasanna Kumar Patil (Aquaculture International, 2021)

DNA interaction, in vivo and in vitro cytotoxicity, reactive oxygen species, lipid peroxidation of –N, S donor Re(I) metal complexes - Reena R. Varma; Juhee G. Pandya; Jyoti Sharma; Chandramani Pathak; Mohan N. Patel (Molecular Diversity, 2021)

Conservation, propagation, and redistribution (CPR) of Hill’s thistle: paradigm for plant species at risk - Wenlu Bi; Akansha Saxena; Murali-Mohan Ayyanath; Cavan Harpur; Mukund R. Shukla; Praveen K. Saxena (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

SSR markers assay-based establishment of distinctness, uniformity and stability of dolichos bean [Lablab purpureus (L.) Sweet var. Lignosus] advanced breeding lines and elite germplasm accessions - Shrikrishna P. Desai; S. Ramesh; P. V. Vaijayanthi; A. Mohan Rao; B. R. Chandana; Basanagouda Gonal (Genetic Resources and Crop Evolution, 2021)

A novel barcode system for rapid identification of rice (Oryza sativa L.) varieties using agro-morphological descriptors and molecular markers - M. Bhargavi; K. Maneesha; D. M. Withanawasam; Kavitha R. Aratikatla; S. Himabindu; M. Prashanth; P. Shanthi; Madhavi L. Kommana; D. Mohan Reddy; B. Ravindra Reddy; Lakshminarayana R. Vemireddy (Molecular Biology Reports, 2021)

Energy and environment - An introduction - Giang Minh Hoang; Wannapawn Watsuntorn; Warawut Chulalaksananukul; Raj Mohan Balakrishnan; Eldon R. Rene (Environmental Science and Pollution Research, 2021)

One Step at a Time: The Origins of Sequential Simulation and Beyond - J. Jaime Gómez-Hernández; R. Mohan Srivastava (Mathematical Geosciences, 2021)
In the mid-1980s, still in his young 40s, André Journel was already recognized as one of the giants of geostatistics. Many of the contributions from his new research program at Stanford University had centered around the indicator methods that he developed: indicator kriging and multiple indicator kriging. But when his second crop of graduate students arrived at Stanford, indicator methods still lacked an approach to conditional simulation that was not tainted by what André called the ‘Gaussian disease’; early indicator simulations went through the tortuous path of converting all indicators to Gaussian variables, running a turning bands simulation, and truncating the resulting multi-Gaussian realizations. When he conceived of sequential indicator simulation (SIS), even André likely did not recognize the generality of an approach to simulation that tackled the simulation task one step at a time. The early enthusiasm for SIS was its ability, in its multiple-indicator form, to cure the Gaussian disease and to build realizations in which spatial continuity did not deteriorate in the extreme values. Much of Stanford’s work in the 1980s focused on petroleum geostatistics, where extreme values (the high-permeability fracture zones and the low-permeability shale barriers) have much stronger anisotropy, and much longer ranges of correlation in the maximum continuity direction, than mid-range values. With multi-Gaussian simulations necessarily imparting weaker continuity to the extremes, SIS was an important breakthrough. The generality of the sequential approach was soon recognized, first through its analogy with multi-variate unconditional simulation achieved using the lower triangular matrix of an LU decomposition of the covariance matrix as the multiplier of random normal deviates. Modifying LU simulation so that it became conditional gave rise to sequential Gaussian simulation (SGS), an algorithm that shared much in common with SIS. With nagging implementation details like the sequential path and the search neighborhood being common to both methods, improvements in either SIS or SGS often became improvements to the other. Almost half of the contributors to this Special Issue became students of André in the classes of 1984–1988, and several are the pioneers of SIS and SGS. Others who studied later with André explored and developed the first multipoint statistics simulation procedures, which are based on the same concept that underlies sequential simulation. Among his many significant intellectual accomplishments, one of the cornerstones of André Journel’s legacy was sequential simulation, built one step at a time.

Introduction to the Special Issue in Honor of André G. Journel - J. Jaime Gómez-Hernández; R. Mohan Srivastava (Mathematical Geosciences, 2021)

A multibiomarker approach to assess lead toxicity on the black clam, Villorita cyprinoides (Gray, 1825), from Cochin estuarine system (CES), southwest coast, India - Kariyil Veettil Neethu; Sivasankaran Bijoy Nandan; Nelkunnassery Dominic Don Xavier; Paravanparambil Rajakumar Jayachandran; Pashnath Raghu Anu; Alungal Manikandan Midhun; Dhandapani Mohan; Shambanagouda R. Marigoudar (Environmental Science and Pollution Research, 2021)

Impact of Boundary Layer Physics on Tropical Cyclone Simulations in the Bay of Bengal Using the WRF Model - J. R. Rajeswari; C. V. Srinivas; P. Reshmi Mohan; B. Venkatraman (Pure and Applied Geophysics, 2020)

Peripheral Blood As a Source of Stem Cells for Regenerative Medicine: Emphasis Towards Corneal Epithelial Reconstruction—An In Vitro Study - Balu Venugopal; Sumitha Mohan; T. V. Kumary; P. R. Anil Kumar (Tissue Engineering and Regenerative Medicine, 2020)

Perchlorate contamination of drinking water sources in Kerala, South India, and its degradation using advanced chemical treatment - M. R. Sijimol; C. T. Aravindakumar; P. R. Manoj; D. Dineep; K. K. Nejumal; Mahesh Mohan (Energy, Ecology and Environment, 2020)

Multi criteria study for seismic hazard assessment of UNESCO world heritage Ahmedabad City, Gujarat, Western India - Vinay Kumar Dwivedi; R. K. Dubey; Vasu Pancholi; Madan Mohan Rout; Pawan Singh; B. Sairam; Sumer Chopra; B. K. Rastogi (Bulletin of Engineering Geology and the Environment, 2020)

Multifractal description of streamflow and suspended sediment concentration data from Indian river basins - S. Adarsh; Drisya S. Dharan; A. R. Nandhu; B. Anand Vishnu; Vysakh K. Mohan; M. Wątorek (Acta Geophysica, 2020)

Individuals in urban dwelling primate species face unequal benefits associated with living in an anthropogenic environment - Pascal R. Marty; Krishna N. Balasubramaniam; Stefano S. K. Kaburu; Josephine Hubbard; Brianne Beisner; Eliza Bliss-Moreau; Nadine Ruppert; Małgorzata E. Arlet; Shahrul Anuar Mohd Sah; Ahmad Ismail; Lalit Mohan; Sandeep K. Rattan; et al. (Primates, 2020)

Random Walk Particle Tracking Embedded Cellular Automata Model for Predicting Temporospatial Variations of Chlorine in Water Distribution Systems - G. R. Abhijith; S. Mohan (Environmental Processes, 2020)

Oceanographic Structure and Light Levels Drive Patterns of Sound Scattering Layers in a Low-Latitude Oceanic System - Kevin M. Boswell; Marta D’Elia; Matthew W. Johnston; John A. Mohan; Joseph D. Warren; R. J. David Wells; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Integration of soil moisture as an auxiliary parameter for the anchor pixel selection process in SEBAL using Landsat 8 and Sentinel - 1A images - M M Prakash Mohan; K Rajitha; Murari R R Varma (International Journal of Remote Sensing, 2020)

Untargeted metabolomics reveals alterations in metabolites of lipid metabolism and immune pathways in the serum of rats after long-term oral administration of Amalaki rasayana - Vikas Kumar; A. Aneesh Kumar; Vinod Joseph; Vipin Mohan Dan; Abdul Jaleel; T. R. Santhosh Kumar; Chandrasekharan C. Kartha (Molecular and Cellular Biochemistry, 2020)

Rapid seismic hazard assessment of the Sabarmati River basin in Gujarat State, Western India using GIS techniques - Nisarg Bhatt; Vasu Pancholi; Sumer Chopra; Madan Mohan Rout; R. D. Shah; Girish Ch. Kothyari (Bulletin of Engineering Geology and the Environment, 2019)

Symbiotic Response of Drought Tolerant Soybean Varieties, DSR 2 and DSR 12 to Different Arbuscular Mycorrhizal Fungi - R. Ashwin; D. J. Bagyaraj; B. Mohan Raju (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Cold treatment prompts embryogenic callus and cytodifferentiation in the anthers of tea (Camellia sp.) genotypes - CH. Naga Pavan Kumar; E. Edwin Raj; P. Mohan Kumar; R. Raj Kumar; K. N. Chandrashekara (Plant Physiology Reports, 2019)

Mixed Pixel Decomposition Based on Extended Fuzzy Clustering for Single Spectral Value Remote Sensing Images - Sumit Kaur; R. K. Bansal; Mamta Mittal; Lalit Mohan Goyal; Iqbaldeep Kaur; Amit Verma; Le Hoang Son (Journal of the Indian Society of Remote Sensing, 2019)

Generalised extreme value model with cyclic covariate structure for analysis of non-stationary hydrometeorological extremes - R S Jagtap; V K Gedam; Mohan M Kale (Journal of Earth System Science, 2019)

Movement, Behavior, and Habitat Use of a Marine Apex Predator, the Scalloped Hammerhead - R. J. David Wells; Thomas C. TinHan; Michael A. Dance; J. Marcus Drymon; Brett Falterman; Matthew J. Ajemian; Gregory W. Stunz; John A. Mohan; Eric R. Hoffmayer; William B. Driggers; Jennifer A. McKinney (Frontiers in Marine Science, 2018)

Linking Habitat Use and Trophic Ecology of Spotted Seatrout (Cynoscion nebulosus) on a Restored Oyster Reef in a Subtropical Estuary - Thomas C. TinHan; John A. Mohan; Mark Dumesnil; Bryan M. DeAngelis; R. J. David Wells (Estuaries and Coasts, 2018)

Mangrove floristics of the Andaman and Nicobar Islands: critical review and current scenario - P. Ragavan; P. M. Mohan; Alok Saxena; R. S. C. Jayaraj; K. Ravichandran; Mani Saxena (Marine Biodiversity, 2018)

Ultradeep single-molecule real-time sequencing of HIV envelope reveals complete compartmentalization of highly macrophage-tropic R5 proviral variants in brain and CXCR4-using variants in immune and peripheral tissues - Robin L. Brese; Maria Paz Gonzalez-Perez; Matthew Koch; Olivia O’Connell; Katherine Luzuriaga; Mohan Somasundaran; Paul R. Clapham; James Jarad Dollar; David J Nolan; Rebecca Rose; Susanna L. Lamers (Journal of NeuroVirology, 2018)

Simultaneous detection and serotyping of dengue infection using single tube multiplex CDC Dengue Real-Time RT-PCR from India - Shashi Sharma; Kundan Tandel; Surabhi Danwe; Puneet Bhatt; P. K. Dash; Praveer Ranjan; K. R. Rathi; Rajiv Mohan Gupta; M. M. Parida (VirusDisease, 2018)

A Tool Assessing Optimal Multi-Scale Image Segmentation - A. Mohan Vamsee; P. Kamala; Tapas R. Martha; K. Vinod Kumar; G. Jai sankar; E. Amminedu (Journal of the Indian Society of Remote Sensing, 2018)

Interaction of coeval felsic and mafic magmas from the Kanker granite, Pithora region, Bastar Craton, Central India - R Elangovan; Kumar Krishna; Neeraj Vishwakarma; K R Hari; M Ram Mohan (Journal of Earth System Science, 2017)

Circulating genotypes of Pneumocystis jirovecii and its clinical correlation in patients from a single tertiary center in India - Y. Singh; B. R. Mirdha; R. Guleria; S. Khalil; A. Panda; R. Chaudhry; A. Mohan; S. K. Kabra; L. Kumar; S. K. Agarwal (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.

Comparative flood area analysis of C-band VH, VV, and L-band HH polarizations SAR data - R. Manavalan; Y. S. Rao; B. Krishna Mohan (International Journal of Remote Sensing, 2017)

Environmental degradation of a tropical estuary due to human interferences—a case study from southern Kerala, SW India - Shiekha E. John; T. R. Rajimol; Vishnu Mohan S; K. Maya; D. Padmalal (Arabian Journal of Geosciences, 2017)

Factors shaping the co-occurrence of two juvenile shark species along the Texas Gulf Coast - Philip Matich; John A. Mohan; Jeffrey D. Plumlee; Tom TinHan; R. J. David Wells; Mark Fisher (Marine Biology, 2017)

Perchlorate in drinking water around rocket manufacturing and testing facilities and firework manufacturing sites in Kerala, India - M. R. Sijimol; V. G. Gopikrishna; D. Dineep; Mahesh Mohan (Energy, Ecology and Environment, 2017)

Evaluation of the Soil Conservation Service curve number methodology using data from agricultural plots - Mohan Lal; S. K. Mishra; Ashish Pandey; R. P. Pandey; P. K. Meena; Anubhav Chaudhary; Ranjit Kumar Jha; Ajit Kumar Shreevastava; Yogendra Kumar (Hydrogeology Journal, 2017)

Analysis of the bacteriorhodopsin-producing haloarchaea reveals a core community that is stable over time in the salt crystallizers of Eilat, Israel - Nikhil Ram-Mohan; Aharon Oren; R. Thane Papke (Extremophiles, 2016)

MicroRNA in aquaculture fishes: a way forward with high-throughput sequencing and a computational approach - Kiran Dashrath Rasal; Priyanka C. Nandanpawar; Pranati Swain; Mohan R. Badhe; Jitendra Kumar Sundaray; Pallipuram Jayasankar (Reviews in Fish Biology and Fisheries, 2016)

Perchlorate contamination in bottled and other drinking water sources of Kerala, southwest coast of India - M. R. Sijimol; Mahesh Mohan; D. Dineep (Energy, Ecology and Environment, 2016)

Summer monsoon onset-induced changes of autotrophic pico- and nanoplankton in the largest monsoonal estuary along the west coast of India - Arya P. Mohan; R. Jyothibabu; L. Jagadeesan; K. R. Lallu; C. Karnan (Environmental Monitoring and Assessment, 2016)

Cell surface interaction of annexin A2 and galectin-3 modulates epidermal growth factor receptor signaling in Her-2 negative breast cancer cells - Praveenkumar Shetty; Anil Bargale; Basavraj R. Patil; Rajashekar Mohan; U. S. Dinesh; Jamboor K. Vishwanatha; Pramod B. Gai; Vidya S. Patil; T. S. Amsavardani (Molecular and Cellular Biochemistry, 2016)

Hydrodynamic behaviour and its effects on the treatment performance of panelled anaerobic baffle-cum filter reactor - R. Renuka; S. Mariraj Mohan; S. Amal Raj (International Journal of Environmental Science and Technology, 2016)

Diversity, distribution and vegetative structure of mangroves of the Andaman and Nicobar Islands, India - P. Ragavan; Alok Saxena; P. M. Mohan; K. Ravichandran; R. S. C. Jayaraj; S. Saravanan (Journal of Coastal Conservation, 2015)

Real-time numerical simulation of tropical cyclone Nilam with WRF: experiments with different initial conditions, 3D-Var and Ocean Mixed Layer Model - Greeshma M. Mohan; C. V. Srinivas; C. V. Naidu; R. Baskaran; B. Venkatraman (Natural Hazards, 2015)

Synthesis and evaluation of new salicylaldehyde-2-picolinylhydrazone Schiff base compounds of Ru(II), Rh(III) and Ir(III) as in vitro antitumor, antibacterial and fluorescence imaging agents - Narasinga Rao Palepu; S. L. Nongbri; J. Richard Premkumar; Akalesh Kumar Verma; Kaushik Bhattacharjee; S. R. Joshi; Scott Forbes; Yurij Mozharivskyj; Romita Thounaojam; K. Aguan; Mohan Rao Kollipara (JBIC Journal of Biological Inorganic Chemistry, 2015)

Histopathological findings on innate responses of white spot disease positive Penaeus monodon (Fabricius) under semi‐intensive culture - A K Sahoo; P C Thakur; K M Shankar; C V Mohan; S R Krupesha Sharma; F Corsin (Journal of Fish Diseases, 2015)

Why do satellite imageries show exceptionally high chlorophyll in the Gulf of Mannar and the Palk Bay during the Norteast Monsoon? - R. Jyothibabu; N. V. Madhu; L. Jagadeesan; A. Anjusha; Arya P. Mohan; N. Ullas; K. Sudheesh; C. Karnan (Environmental Monitoring and Assessment, 2014)

Environmental impacts of perchlorate with special reference to fireworks—a review - M. R. Sijimol; Mahesh Mohan (Environmental Monitoring and Assessment, 2014)

GSL2 over-expression confers resistance to Pectobacterium atrosepticum in potato - Sara Mohan; Sathiyamoorthy Meiyalaghan; Julie M. Latimer; Michelle L. Gatehouse; Katrina S. Monaghan; Bhanupratap R. Vanga; Andrew R. Pitman; E. Eirian Jones; Anthony J. Conner; Jeanne M. E. Jacobs (Theoretical and Applied Genetics, 2014)

The N-terminal region containing the zinc finger domain of tobacco streak virus coat protein is essential for the formation of virus-like particles - Chhavi Mathur; Kalyani Mohan; T. R. Usha Rani; M. Krishna Reddy; Handanahal S. Savithri (Archives of Virology, 2014)

Storm surge vulnerability along Chennai–Cuddalore coast due to a severe cyclone THANE - V. Ranga Rao; B. R. Subramanian; R. Mohan; R. Kannan; T. Mageswaran; T. Arumugam; B. Rajan (Natural Hazards, 2013)

Mapping QTL for grain yield and other agronomic traits in post-rainy sorghum [Sorghum bicolor (L.) Moench] - R. Nagaraja Reddy; R. Madhusudhana; S. Murali Mohan; D. V. N. Chakravarthi; S. P. Mehtre; N. Seetharama; J. V. Patil (Theoretical and Applied Genetics, 2013)

Deep transcriptome sequencing reveals the expression of key functional and regulatory genes involved in the abiotic stress signaling pathways in rice - R. C. Venu; M. V. Sreerekha; M. Sheshu Madhav; Kan Nobuta; K. Madhan Mohan; Songbiao Chen; Yulin Jia; Blake C. Meyers; Guo-Liang Wang (Journal of Plant Biology, 2013)

Assessment of urban heat island effect for different land use–land cover from micrometeorological measurements and remote sensing data for megacity Delhi - Manju Mohan; Yukihiro Kikegawa; B. R. Gurjar; Shweta Bhati; Narendra Reddy Kolli (Theoretical and Applied Climatology, 2013)

The influence of Indian Ocean sea surface temperature on the variability of monsoon rainfall over India - Lorna R. Nayagam; J. Rajesh; H. S. Ram Mohan (International Journal of Climatology, 2013)
This study focuses on the spatial and temporal variability of southwest monsoon (SWM) and northeast monsoon (NEM) rainfall over India, after the 1976–1977 regime shift. Through wavelet analysis the dominant mode of variability in the SWM and NEM rainfall is found to be in the 2–8‐year scale (ENSO band). Therefore, scale‐averaged wavelet power (SAP) of SWM (SAPSWM) and NEM (SAPNEM) rainfall obtained from a high‐resolution dataset for the period 1977–2001 was subjected to empirical orthogonal function analysis, in order to understand the homogenous regions of rainfall variability. As the study utilizes SAP, the decadal variability is observed in the spatial and temporal patterns of rainfall. The maximum variability of SAPSWM rainfall is found to be in the 2–4‐year period, whereas, for the SAPNEM rainfall, the biennial mode explains the variability over the core region of NEM rainfall. Significant power is also observed in the 4‐year period. The evolution of the principal components (PCs) is consistent with the above/below normal rainfall received over the region. Similar analysis has been carried out also for the SAP of monthly sea surface temperature (SAPSST) over Indian Ocean for the months from January to September. Compared with any other month, the decadal changes of the PCs of SAPSWM and SAPNEM rainfall are highly correlated with the decadal variations of PC1 of SAPSST for the month of March. Therefore, the relation between the rainfall and SST was explained using SAPSST for the month of March. Significant biennial power is also observed in March SST over southeast Indian Ocean (85–110°E and 5–40°S) after the climate shift of 1976. In order to identify any change in the relation between NEM rainfall and SAPSST (March) before and after 1976, a correlation between NEM rainfall and PC1 of SAPSST (March) was found for the period 1951–1975 and 1977–2001. Results show that correlation has increased after 1976. Therefore, this PC can be made use of in the prediction of NEM rainfall. Copyright © 2012 Royal Meteorological Society

Multiple Approaches Towards Decolorization and Reuse of a Textile Dye (VB-B) by a Marine Bacterium Shewanella decolorationis - S. Satheesh Babu; C. Mohandass; A. S. Vijay Raj; R. Rajasabapathy; Mohan A. Dhale (Water, Air, & Soil Pollution, 2013)

Fentanyl-associated Fatalities Among Illicit Drug Users in Wayne County, Michigan (July 2005–May 2006) - D. Adam Algren; Carolyn P. Monteilh; Mohan Punja; Joshua G. Schier; Martin Belson; Bradford R. Hepler; Carl J. Schmidt; Corinne E. Miller; Manish Patel; Leonard J. Paulozzi; Masja Straetemans; Carol Rubin (Journal of Medical Toxicology, 2013)

Cell sorting analysis of geographically separated hypersaline environments - Olga Zhaxybayeva; Ramunas Stepanauskas; Nikhil Ram Mohan; R. Thane Papke (Extremophiles, 2013)

Observed Variability of Thermohaline Fields, Currents and Eddies in the Western Bay of Bengal During BOBMEX-99 - P. V. Hareesh Kumar; N. Mohan Kumar; T. N. Shyni; A. R. Rao (Marine Geodesy, 2013)

New distributional record of buff coconut mealybug (Nipaecoccus nipae) in Kerala, India - A. Josephrajkumar; P. Rajan; Chandrika Mohan; R. J. Thomas (Phytoparasitica, 2012)

Association mapping for pre-harvest sprouting tolerance in common wheat (Triticum aestivum L.) - V. Jaiswal; R. R. Mir; A. Mohan; H. S. Balyan; P. K. Gupta (Euphytica, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Observational study of cloud base height and its frequency over a tropical station, Thiruvananthapuram, using a ceilometer - Hamza Varikoden; R. Harikumar; R. Vishnu; V. Sasi Kumar; S. Sampath; S. Murali Das; G. Mohan Kumar (International Journal of Remote Sensing, 2011)

Associations of serum vitamin A and carotenoid levels with markers of prostate cancer detection among US men - Hind A. Beydoun; Monal R. Shroff; Ravinder Mohan; May A. Beydoun (Cancer Causes & Control, 2011)

Petroleum hydrocarbon concentrations in ten commercial fish species along Tamilnadu coast, Bay of Bengal, India - S. Veerasingam; R. Venkatachalapathy; P. Raja; S. Sudhakar; V. Rajeswari; R. Mohamed Asanulla; R. Mohan; P. Sutharsan (Environmental Science and Pollution Research, 2011)

Korean ginseng extract attenuates reserpine-induced orofacial dyskinesia and improves cognitive dysfunction in rats - Chetankumar R. Sanghavi; Shrikant A. Barhate; Manoj S. Mahajan; Mahalaxmi Mohan; Sanjay B. Kasture (Natural Product Research, 2011)

Archaean gold mineralization synchronous with late cratonization of the Western Dharwar Craton, India: 2.52 Ga U–Pb ages of hydrothermal monazite and xenotime in gold deposits - D. Srinivasa Sarma; Ian R. Fletcher; Birger Rasmussen; Neal J. McNaughton; M. Ram Mohan; David I. Groves (Mineralium Deposita, 2011)

First record of Asian grey weevil (Myllocerus undatus) on coconut from Kerala, India - A. Josephrajkumar; P. Rajan; Chandrika Mohan; R. J. Thomas (Phytoparasitica, 2011)

Exploitation of the late flowering species Brassica oleracea L. for the improvement of earliness in B. napus L.: an untraditional approach - M. Habibur Rahman; Rick A. Bennett; Rong-Cai Yang; Berisso Kebede; Mohan R. Thiagarajah (Euphytica, 2011)

Network of earthquakes and recurrences therein - T. R. Krishna Mohan; P. G. Revathi (Journal of Seismology, 2011)

Chemical constituents of the essential oil from Dysoxylum malabaricum Bedd. wood of Western Ghats, India - S. Mohan; R. Ezhumalai; S. H. Jain; G. Ravikumar (Journal of the Indian Academy of Wood Science, 2010)

Complete nucleotide sequence of cherry virus A (CVA) infecting sweet cherry in India - M. S. Noorani; P. Awasthi; Rahul Mohan Singh; Raja Ram; M. P. Sharma; S. R. Singh; N. Ahmed; V. Hallan; A. A. Zaidi (Archives of Virology, 2010)

Identification of quantitative trait loci associated with resistance to foliar diseases in sorghum [Sorghum bicolor (L.) Moench] - S. Murali Mohan; R. Madhusudhana; K. Mathur; D. V. N. Chakravarthi; Sanjay Rathore; R. Nagaraja Reddy; K. Satish; G. Srinivas; N. Sarada Mani; N. Seetharama (Euphytica, 2010)

Land-cover change dynamics and coastal aquaculture development: a case study in the East Godavari delta, Andhra Pradesh, India using multi-temporal satellite data - K. Rajitha; C. K. Mukherjee; R. Vinu Chandran; M. M. Prakash Mohan (International Journal of Remote Sensing, 2010)

Evaluation of SSR Markers for the Assessment of Genetic Diversity and Fingerprinting of Gossypium hirsutum Accessions - Arunita Rakshit; S. Rakshit; V. Santhy; V. P. Gotmare; P. Mohan; V. V. Singh; S. Singh; J. Singh; H. S. Balyan; P. K. Gupta; S. R. Bhat (Journal of Plant Biochemistry and Biotechnology, 2010)

Erratum to: Comparative study of experimental foot-and-mouth disease in cattle (Bos indicus) and buffaloes (Bubalus bubalis) - Mohan S. Maddur; Mukund R. Gajendragad; Susurla Gopalakrishna; Nem Singh (Veterinary Research Communications, 2010)

Identification of quantitative trait loci for resistance to shoot fly in sorghum [Sorghum bicolor (L.) Moench] - K. Satish; G. Srinivas; R. Madhusudhana; P. G. Padmaja; R. Nagaraja Reddy; S. Murali Mohan; N. Seetharama (Theoretical and Applied Genetics, 2009)

Relative Microalgal Concentration in Prydz Bay, East Antarctica during Late Austral Summer, 2006 - Rahul Mohan; Sunil Kumar Shukla; N. Anilkumar; M. Sudhakar; Satya Prakash; R. Ramesh (Algae, 2009)

Decreased mass specific respiration under experimental warming is robust to the microbial biomass method employed - Mark A. Bradford; Matthew D. Wallenstein; Steven D. Allison; Kathleen K. Treseder; Serita D. Frey; Brian W. Watts; Christian A. Davies; Thomas R. Maddox; Jerry M. Melillo; Jacqueline E. Mohan; James F. Reynolds (Ecology Letters, 2009)
Hartley et al. question whether reduction in R mass , under experimental warming, arises because of the biomass method. We show the method they treat as independent yields the same result. We describe why the substrate‐depletion hypothesis may not solely explain observed responses, and urge caution in interpretation of the seasonal data.

Identification of quantitative trait loci for agronomically important traits and their association with genic-microsatellite markers in sorghum - G. Srinivas; K. Satish; R. Madhusudhana; R. Nagaraja Reddy; S. Murali Mohan; N. Seetharama (Theoretical and Applied Genetics, 2009)

Comparative study of experimental foot-and-mouth disease in cattle (Bos indicus) and buffaloes (Bubalis bubalus) - Mohan S. Maddur; Mukund R. Gajendragad; Susurla Gopalakrishna; Nem Singh (Veterinary Research Communications, 2009)

Kinetics of immune response to foot-and-mouth disease virus (type Asia 1) in experimental cattle - Mohan S. Maddur; Mukund R. Gajendragad; Subodh Kishore; Susurla Gopalakrishna; Nem Singh (Veterinary Research Communications, 2009)

Burnt area mapping of Bandipur National Park, India using IRS 1C/1D LISS III data - R. K. Somashekar; P. Ravikumar; C. N. Mohan Kumar; K. L. Prakash; B. C. Nagaraja (Journal of the Indian Society of Remote Sensing, 2009)

Nitrilase-catalysed conversion of acrylonitrile by free and immobilized cells of Streptomyces sp. - V. K. Nigam; A. K. Khandelwal; R. K. Gothwal; M. K. Mohan; B. Choudhury; A. S. Vidyarthi; P. Ghosh (Journal of Biosciences, 2009)

Kinetics of immune response to foot-and-mouth disease virus (type Asia 1) in experimental cattle - M. S. Mohan; M. R. Gajendragad; Subodh Kishore; S. Gopalakrishna; Nem Singh (Veterinary Research Communications, 2009)

Origin and characterisation of microparticles in an ice core from the Central Dronning Maud Land, East Antarctica - C. M. Laluraj; K. P. Krishnan; M. Thamban; R. Mohan; S. S. Naik; W. D’Souza; R. Ravindra; A. Chaturvedi (Environmental Monitoring and Assessment, 2009)

Estimation of forest biophysical variables from Indian Earth Observation Satellite Cartosat‐1 stereo data - M. M. Kimothi; S. Mohan; R. B. Singh; P. Soni; H. B. Vashistha; Ajai (International Journal of Remote Sensing, 2009)

Thermal adaptation of soil microbial respiration to elevated temperature - Mark A. Bradford; Christian A. Davies; Serita D. Frey; Thomas R. Maddox; Jerry M. Melillo; Jacqueline E. Mohan; James F. Reynolds; Kathleen K. Treseder; Matthew D. Wallenstein (Ecology Letters, 2008)
In the short‐term heterotrophic soil respiration is strongly and positively related to temperature. In the long‐term, its response to temperature is uncertain. One reason for this is because in field experiments increases in respiration due to warming are relatively short‐lived. The explanations proposed for this ephemeral response include depletion of fast‐cycling, soil carbon pools and thermal adaptation of microbial respiration. Using a > 15 year soil warming experiment in a mid‐latitude forest, we show that the apparent ‘acclimation’ of soil respiration at the ecosystem scale results from combined effects of reductions in soil carbon pools and microbial biomass, and thermal adaptation of microbial respiration. Mass‐specific respiration rates were lower when seasonal temperatures were higher, suggesting that rate reductions under experimental warming likely occurred through temperature‐induced changes in the microbial community. Our results imply that stimulatory effects of global temperature rise on soil respiration rates may be lower than currently predicted.

Interspecific cross of Brassica oleracea var. alboglabra and B. napus: effects of growth condition and silique age on the efficiency of hybrid production, and inheritance of erucic acid in the self-pollinated backcross generation - Rick A. Bennett; Mohan R. Thiagarajah; Jane R. King; M. Habibur Rahman (Euphytica, 2008)

Development of tomato hybrids resistant to tomato leaf curl virus disease in South India - K. S. Shankarappa; Sriharsha; K. T. Rangaswamy; D. S. Aswathanarayana; H. A. Prameela; R. S. Kulkarni; V. Muniyappa; A. Mohan Rao; M. N. Maruthi (Euphytica, 2008)

Comparative study of experimental Foot-and-Mouth Disease in cattle (Bos indicus) and buffaloes (Bubalis bubalus) - M. S. Mohan; M. R. Gajendragad; S. Gopalakrishna; Nem Singh (Veterinary Research Communications, 2008)

Development of genic-microsatellite markers for sorghum staygreen QTL using a comparative genomic approach with rice - G. Srinivas; K. Satish; S. Murali Mohan; R. Nagaraja Reddy; R. Madhusudhana; D. Balakrishna; B. Venkatesh Bhat; C. J. Howarth; N. Seetharama (Theoretical and Applied Genetics, 2008)

Hormone receptor-related gene polymorphisms and prostate cancer risk in North Indian population - Khadijeh Onsory; R. C. Sobti; Adnan Issa Al-Badran; Masatoshi Watanabe; Taizo Shiraishi; Awtar Krishan; Harsh Mohan; Pushpinder Kaur (Molecular and Cellular Biochemistry, 2008)

Genetic Diversity Analysis of Starchy Curcuma Species Using RAPD Markers - G. R. Angel; T. Makeshkumar; C. Mohan; B. Vimala; B. Nambisan (Journal of Plant Biochemistry and Biotechnology, 2008)

A novel association of a polymorphism in the first intron of adiponectin gene with type 2 diabetes, obesity and hypoadiponectinemia in Asian Indians - Karani S. Vimaleswaran; Venkatesan Radha; Kandaswamy Ramya; Hunsur Narayan Sathish Babu; Nageshappa Savitha; Venkataramaiah Roopa; Dhar Monalisa; Raj Deepa; Saurabh Ghosh; Partha P. Majumder; M. R. Sathyanarayana Rao; Viswanathan Mohan (Human Genetics, 2008)

Differential Regulation of the Renin-Angiotensin System by Nicotine in WKY and SHR Glia - Merari F. R. Ferrari; Mohan K. Raizada; Debora R. Fior-Chadi (Journal of Molecular Neuroscience, 2008)

High doses of dietary zinc induce cytokines, chemokines, and apoptosis in reproductive tissues during regression - N. R. Sundaresan; D. Anish; K. V. H. Sastry; V. K. Saxena; K. Nagarajan; J. Subramani; M. D. M. Leo; N. Shit; J. Mohan; M. Saxena; K. A. Ahmed (Cell and Tissue Research, 2008)

An empirical model for the seasonal prediction of southwest monsoon rainfall over Kerala, a meteorological subdivision of India - Lorna R. Nayagam; Rajesh Janardanan; H. S. Ram Mohan (International Journal of Climatology, 2008)
There are several studies showing a skillful empirical prediction of the All India Summer Monsoon Rainfall (AISMR) based on various combination of parameters as the predictors. However, the southwest monsoon rainfall over Kerala, a meteorological subdivision of India, bears a considerably low correlation coefficient with the AISMR. This implies that the existing predictors in the long‐range forecast models of the AISMR do not have much influence on the Kerala Summer Monsoon Rainfall (KSMR). This study attempts to examine the relationship of some ocean and atmospheric parameters with the rainfall and to formulate a linear multiple regression model for the long‐range forecast over a small area like the Kerala. Parameters having significant correlation (significant at 1% level) with the KSMR were identified for the period 1961–1994. The consistency of the relationship between these parameters and the KSMR was checked by doing a 21‐year sliding window correlation (significant at 5% level). Using a stepwise regression method, seven predictors, explaining a significant amount of variance in the KSMR were selected and a linear multiple regression model was developed. The parameters that explain the high inter‐annual variability of the KSMR are specific humidity, sensible heat net flux, relative humidity, zonal wind at 70 and 10 hPa, meridional wind and geopotential height. The characteristics of the forecast and its reliability were studied by various statistical techniques such as, Durbin Watson statistics and variance inflation factor. The model has a multiple correlation of 0.943 and coefficient of determination of 88.8%. The root mean square error (RMSE) was 6.60% (15.80%), bias (BIAS) was − 0.26% (6.20%), absolute error (ABSE) was 5.33% (13.15%) of mean rainfall for the training (test) period respectively. Climatological predictions were also made and the RMSE was (17.90%), BIAS (−5.40%) and ABSE (15.16%) of mean rainfall. The selected parameters were at least 2 months prior to the monsoon season and hence have predictive value. Copyright © 2007 Royal Meteorological Society

Nicotine Modulates the Renin–Angiotensin System of Cultured Neurons and Glial Cells from Cardiovascular Brain Areas of Wistar Kyoto and Spontaneously Hypertensive Rats - Merari F. R. Ferrari; Mohan K. Raizada; Debora R. Fior-Chadi (Journal of Molecular Neuroscience, 2007)

A deterministic approach for preparation of seismic hazard maps in North East India - A. Joshi; Kapil Mohan; R. C. Patel (Natural Hazards, 2007)

Effect of Therapy on Serum Zinc and Copper in Primary Complex of Children - G. Mohan; S. Kulshreshtha; R. Dayal; M. Singh; P. Sharma (Biological Trace Element Research, 2007)

Preparation and Validation of Gridded Emission Inventory of Criteria Air Pollutants and Identification of Emission Hotspots for Megacity Delhi - Manju Mohan; Lalit Dagar; B. R. Gurjar (Environmental Monitoring and Assessment, 2007)

Seasonal variation of pteropods from the Western Arabian Sea sediment trap - R. Mohan; K. Verma; L. P. Mergulhao; D. K. Sinha; S. Shanvas; M. V. S. Guptha (Geo-Marine Letters, 2006)

Sequence diversity of the nucleoprotein gene of iris yellow spot virus (genus Tospovirus, family Bunyaviridae) isolates from the western region of the United States - H. R. Pappu; L. J. du Toit; H. F. Schwartz; S. K. Mohan (Archives of Virology, 2006)

Brain Uptake of Nonsteroidal Anti-Inflammatory Drugs: Ibuprofen, Flurbiprofen, and Indomethacin - Jagan Mohan R. Parepally; Haritha Mandula; Quentin R. Smith (Pharmaceutical Research, 2006)

Detecting and estimating segregation distortion and linkage between glufosinate tolerance and blackleg resistance in Brassica napus L. - Rong-Cai Yang; Mohan R. Thiagarajah; Vipan K. Bansal; Gary R. Stringam; M. Habibur Rahman (Euphytica, 2006)

Changes in the source and transport mechanism of terrigenous input to the Indian sector of Southern Ocean during the late Quaternary and its palaeoceanographic implications - M. Thamban; S. S. Naik; R. Mohan; A. Rajakumar; N. Basavaiah; Witty D’Souza; Sarita Kerkar; M. M. Subramaniam; M. Sudhakar; P. C. Pandey (Journal of Earth System Science, 2005)

Heavy Metal Pollution Assessment in Surface Water Bodies and its Suitability for Irrigation around the Neyevli Lignite Mines and Associated Industrial Complex, Tamil Nadu, India - R. Khan; S. H. Israili; H. Ahmad; A. Mohan (Mine Water and the Environment, 2005)

Differential gene expression during teliospore germination in Ustilago maydis - Ali R. Zahiri; Mohan R. Babu; Barry J. Saville (Molecular Genetics and Genomics, 2005)

Promoter Trapping in Arabidopsis Using T-DNA Insertional Mutagenesis - Radhamony Resminath; Anand Mohan Prasad; Dhiraj R. Thakare; C. Sivanandan; S. R. Bhat; Srinivasan (Journal of Plant Biochemistry and Biotechnology, 2005)

Distribution of Persistent Organochlorine Pesticide Residues in Gomti River, India - K. P. Singh; A. Malik; D. Mohan; R. Takroo (Bulletin of Environmental Contamination and Toxicology, 2005)

Tagging and mapping of a rice gall midge resistance gene, Gm8, and development of SCARs for use in marker-aided selection and gene pyramiding - A. Jain; R. Ariyadasa; A. Kumar; M. N. Srivastava; M. Mohan; S. Nair (Theoretical and Applied Genetics, 2004)

Biotransformation of Externally Added Vanillin Related Compounds by Multiple Shoot Cultures of Vanilla planifolia L - Meera H. Velankar; Mohan R. Heble (Journal of Plant Biochemistry and Biotechnology, 2004)

Use of sugarcane bagasse as an alternative low-cost support material during the rooting stage of apple micropropagation - R. Mohan; C. R. Soccol; M. Quoirin; A. Pandey (In Vitro Cellular & Developmental Biology - Plant, 2004)

Floral sexuality and breeding system in gum karaya tree, Sterculia urens - V. G. Sunnichan; H. Y. Mohan Ram; K. R. Shivanna (Plant Systematics and Evolution, 2004)

Curcumin-induced inhibition of cellular reactive oxygen species generation: Novel therapeutic implications - M. Balasubramanyam; A. Adaikala Koteswari; R. Sampath Kumar; S. Finny Monickaraj; J. Uma Maheswari; V. Mohan (Journal of Biosciences, 2003)

Regulation of tissue factor-factor VIIa expression on cell surfaces: A role for tissue factor-factor VIIa endocytes - L. Vijaya Mohan Rao; Usha R. Pendurthi (Molecular and Cellular Biochemistry, 2003)

Induction of systemic resistance to Xanthomonas oryzae pv. oryzae by salicylic acid in Oryza sativa (L.) - R. Mohan Babu; A. Sajeena; A. Vijaya Samundeeswari; A. Sreedhar; P. Vidhyasekaran; K. Seetharaman; M. S. Reddy (Journal of Plant Diseases and Protection, 2003)

Potential predictability of the Asian summer monsoon on monthly and seasonal time scales - R. S. Ajaya Mohan; B. N. Goswami (Meteorology and Atmospheric Physics, 2003)

Toxicology and free radicals scavenging property of Tamra bhasma - N. Pattanaik; Ajita V Singh; R. S. Pandey; B. S. Singh; Mohan Kumar; S. K. Dixit; Yamini B. Tripathi (Indian Journal of Clinical Biochemistry, 2003)

Characterization of a phytotoxic glycoprotein produced byPhoma eupyrena — A pathogen on water lettuce - R. Mohan Babu; A. Sajeena; P. Vidhyasekaran; K. Seetharaman; M. S. Reddy (Phytoparasitica, 2003)

Potential Health Risks Due to Toxic Contamination in the Ambient Environment of Certain Indian States - B. R. Gurjar; Manju Mohan (Environmental Monitoring and Assessment, 2003)

Alternaria alternata toxin detection by fluorescence derivatization and separation by high performance liquid chromatography - R. Mohan Babu; A. Sajeena; K. Seetharaman; P. Rangasamy; E. G. Ebenezer; P. Vidhyasekaran (Phytoparasitica, 2003)

In vivo evaluation of modified gum karaya as a carrier for improving the oral bioavailability of a poorly water-soluble drug, nimodipine - Gedela V. Murali Mohan Babu; Namballa R. Kumar; Kasina H. Sankar; Battu J. Ram; Namburu K. Kumar; Kolapalli V. R. Murthy (AAPS PharmSciTech, 2002)

Comparison of ocean color chlorophyll algorithms for IRS-P4 OCM sensor usingin-situ data - Prakash Chauhan; M Mohan; S R Nayak; R R Navalgund (Journal of the Indian Society of Remote Sensing, 2002)

Carbon Stock, Afforestation and Acidic Deposition: An Analysis of Inter-Relation with Reference to Arid Areas - Sanjay Kumar; R. Datta; S. Sinha; T. Kojima; S. Katoh; M. Mohan (Water, Air, & Soil Pollution, 2001)

Tracing mangrove carbon in suspended matter and aquatic fauna of the Gautami–Godavari Delta, Bay of Bengal (India) - F. Dehairs; R. G. Rao; P. Chandra Mohan; A.V. Raman; S. Marguillier; L. Hellings (Hydrobiologia, 2000)

Isolation of two antifungal compounds fromNeolitsea cuipala and their activity against some plant pathogenic fungi - P. Boruah; P. Deka Bhuyan; S. C. Dutta; S. Mohan; R. K. Mathur (Folia Microbiologica, 1999)

Resistance gene analogues from rice: cloning, sequencing and mapping - R. Mago; S. Nair; M. Mohan (Theoretical and Applied Genetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Micropropagation of gum karaya ( Sterculia urens ) by adventitious shoot formation and somatic embryogenesis - V. G. Sunnichan; K. R. Shivanna; H. Y. Mohan Ram (Plant Cell Reports, 1998)

Isolation and FISH mapping of Yeast Artificial Chromosomes (YACs) encompassing an allele of the Gm2 gene for gall midge resistance in rice - K. R. Rajyashri; S. Nair; N. Ohmido; K. Fukui; N. Kurata; T. Sasaki; M. Mohan (Theoretical and Applied Genetics, 1998)

Role of Godavari mangroves (India) in the production and survival of prawn larvae - P. Chandra Mohan; R. G. Rao; F. Dehairs (Hydrobiologia, 1997)

Development and Field Performance of a Sporeless Mutant of Bacillus thuringiensis Subsp. kurstaki - K. S. Mohan; R. Asokan; C. Gopalakrishnan (Journal of Plant Biochemistry and Biotechnology, 1997)

Infection of aerial parts of potato plants byColletotrichum cocodes and its effects on premature vine death and yield - S. K. Mohan; J. R. Davis; L. H. Sorensen; A. T. Schneider (American Journal of Potato Research, 1993)

Infection of aerial parts of potato plants byColletotrichum coccodes and its effects on premature vine death and yield - S. K. Mohan; J. R. Davis; L. H. Sorensen; A. T. Schneider (American Journal of Potato Research, 1992)

Oxidation of tricarboxylic acid cycle intermediates byStreptomyces nitrificans - Albert Schatz; R. Ram Mohan; Gilbert S. Trelawny (Antonie van Leeuwenhoek, 1955)